Exhaust gas treatment system for treating exhaust gas stream exiting gasoline engine
By using porous oxidation material catalysts and SCR catalysts loaded with platinum group metals in the exhaust gas treatment system, the problem of difficulty in reducing ammonia, hydrocarbons and carbon monoxide emissions in the prior art is solved, effectively controlling tailpipe emissions is achieved, and stricter emission regulations are met.
Patent Information
- Application Number
- CN202380050887.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-04
- Filing Date
- 2023-07-03
- Publication Date
- 2025-03-04
AI Technical Summary
Existing exhaust gas treatment systems are difficult to effectively reduce tailpipe emissions from ammonia (NH3), hydrocarbons (HC) and carbon monoxide (CO), especially when facing stricter emission regulations.
An exhaust gas treatment system consisting of a three-effect conversion catalyst, a four-effect conversion catalyst and a selective catalytic reduction (SCR) catalyst is used. These catalysts combine zeolite materials and non-zeolite oxidizing materials in the SCR coating to form an efficient exhaust gas treatment system by loading the platinum group metal components on the porous oxidizing materials.
The ammonia, hydrocarbons and carbon monoxide in the tailpipe emissions have been significantly reduced, especially HC emissions from low-temperature HC ignition activity, meeting stricter emission standards.
Smart Images

Figure HDA0005217552040000011 
Figure HDA0005217552040000021 
Figure HDA0005217552040000031
Abstract
Description
[0001] The present invention relates to an exhaust gas treatment system for treating an exhaust gas flow leaving a gasoline engine and a method for treating an exhaust gas flow leaving a gasoline engine using said exhaust gas treatment system.
[0002] Emission regulations for exhaust gases from mobile gasoline applications have become increasingly stringent in the past and may lead to even more stringent regulations in the future. Therefore, more effective exhaust gas treatment systems for automobiles will be needed in the coming years. In the past, effective ways to remove the main pollutants including nitrogen oxides (NOx), unburned hydrocarbons (HC), carbon monoxide (CO) and particulate matter from gasoline engines have been developed and commercialized based on so-called three-way conversion catalysts (TWC) or four-way conversion catalysts (FWC).
[0003] However, future emission regulations may also impose stricter limits on secondary emissions from the exhaust gas. For example, stricter European emission standards such as EURO 7 or comparable regulations in the United States may impose limits on ammonia (NH3), hydrocarbons (HC) and carbon monoxide (CO) tailpipe emissions.
[0004] Studies have shown that such components have harmful effects on humans, ecosystems and vegetation.Therefore, there is a need to provide improved exhaust gas treatment systems that allow for the reduction of tailpipe emissions of ammonia (NH3), hydrocarbons (HC) and carbon monoxide (CO).
[0005] It is therefore an object of the present invention to provide an improved exhaust gas treatment system for treating the exhaust gas flow leaving a gasoline engine, which exhaust gas treatment system allows a reduction in ammonia (NH3), hydrocarbons (HC) and / or carbon monoxide (CO) tailpipe emissions compared to systems according to the prior art (e.g. EURO 6 or other systems). In addition to improved ammonia tailpipe emissions, it has been found that the system of the invention makes a significant contribution to the reduction of HC emissions, mainly resulting from a robust low-temperature HC light-off activity.
[0006] Thus, the present invention relates to an exhaust gas treatment system for treating an exhaust gas flow leaving a gasoline engine, the exhaust gas treatment system having an upstream end for introducing the exhaust gas flow into the exhaust gas treatment system, wherein the exhaust gas treatment system comprises
[0007] (i) a first catalyst, the first catalyst being a three-way conversion catalyst having an inlet end and an outlet end and comprising a coating disposed on a substrate, wherein the coating comprises a platinum group metal component supported on a porous oxidic material;
[0008] (ii) a second catalyst that is a four-way conversion catalyst having an inlet end and an outlet end and comprising a washcoat disposed on a wall flow filter substrate, wherein the washcoat comprises a platinum group metal component supported on a porous oxidic material;
[0009] (iii) a third catalyst having an inlet end and an outlet end, wherein the third catalyst comprises a substrate and a washcoat for selective catalytic reduction of NOx, wherein the SCR washcoat comprises a zeolite material comprising one or more of Fe and Cu, wherein at most 0.0001 wt. % of the SCR washcoat consists of a platinum group metal;
[0010] wherein the first catalyst according to (i) is the first catalyst of the exhaust treatment system downstream of the upstream end of the exhaust treatment system, and wherein the inlet end of the first catalyst is arranged upstream of the outlet end of the first catalyst;
[0011] wherein in the exhaust gas treatment system, the second catalyst according to (ii) is located downstream of the first catalyst according to (i), and wherein the inlet end of the second catalyst is arranged upstream of the outlet end of the second catalyst;
[0012] Wherein in the exhaust gas treatment system, the third catalyst according to (iii) is located downstream of the second catalyst according to (ii), and wherein the inlet end of the third catalyst is arranged upstream of the outlet end of the third catalyst.
[0013] Preferably, the outlet end of the first catalyst according to (i) is fluidly connected to the inlet end of the second catalyst according to (ii), and wherein between the outlet end of the first catalyst according to (i) and the inlet end of the second catalyst according to (ii), no catalyst for treating the exhaust gas flow leaving the first catalyst is located in the exhaust treatment system.
[0014] Preferably, the outlet end of the second catalyst according to (ii) is fluidly connected to the inlet end of the third catalyst according to (iii), and wherein between the outlet end of the second catalyst according to (ii) and the inlet end of the third catalyst according to (iii), no catalyst for treating the exhaust gas flow leaving the second catalyst is located in the exhaust treatment system.
[0015] First Catalyst
[0016] Preferably, the platinum group metal component of the washcoat of the first catalyst comprises one or more of Pd, Rh and Pt, more preferably one or more of Pd and Rh, more preferably Pd and Rh.
[0017] Preferably, the coating of the first catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 200g / ft 3 In the range of 20 g / ft 3 Up to 180g / ft 3In the range of 50 g / ft 3 Up to 150g / ft 3 The platinum group metal component is within the range of.
[0018] Preferably, the porous oxide material of the platinum group metal component of the coating layer supporting the first catalyst is selected from the group consisting of alumina, ceria, silica, zirconia, titania, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of alumina, titania, zirconia, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of alumina, zirconia, a mixture of two of them and a mixed oxide of two of them, more preferably alumina.
[0019] Preferably, the first catalyst contains 0.2 g / in 3 Up to 4.0g / in 3 In the range of 0.3 g / in 3 Up to 3.0g / in 3 In the range of 0.4 g / in 3 Up to 2.5g / in 3 and even more preferably in the range of 0.5 g / in 3 Up to 2.0g / in 3 A range of porous oxide materials for coatings.
[0020] Preferably, the coating of the first catalyst further comprises an oxygen storage component, which oxygen storage component more preferably comprises cerium, more preferably comprises one or more of cerium oxide, a mixture of oxides including cerium oxide and a mixed oxide comprising cerium, wherein the mixed oxide comprising cerium more preferably further comprises one or more of zirconium, yttrium, neodymium, lanthanum, hafnium, samarium and praseodymium, more preferably one or more of zirconium, yttrium, neodymium, lanthanum and praseodymium, more preferably zirconium.
[0021] Preferably, the oxygen storage component of the coating of the first catalyst comprises a mixed oxide comprising cerium and zirconium.
[0022] Preferably, 95% to 100% by weight, more preferably 98% to 100% by weight, more preferably 99% to 100% by weight, more preferably 99.5% to 100% by weight of the oxygen storage component consists of a mixed oxide containing cerium and zirconium.
[0023] Preferably 10 to 60 wt%, more preferably 20 to 60 wt%, more preferably 20 to 50 wt% of the oxygen storage component consists of cerium calculated as CeO2, and preferably 20 to 90 wt%, more preferably 40 to 70 wt%, more preferably 50 to 70 wt% of the oxygen storage component consists of zirconium calculated as ZrO2. Preferably 0 to 20 wt%, more preferably 0 to 10 wt% of the OSC consists of lanthanum and yttrium calculated as La2O3 and Y2O3.
[0024] Preferably, the first catalyst coating comprises a loading of 0.3 g / in 3 Up to 5g / in 3 In the range of 0.4 g / in 3 Up to 3.5g / in 3 In the range of 0.45 g / in 3 Up to 3.0g / in 3 In the range of 0.5 g / in 3 Up to 2.5g / in 3 Oxygen storage components within the range.
[0025] Preferably, in the coating of the first catalyst, the weight ratio of the porous oxidic material as defined above to the oxygen storage component is in the range of 1:1 to 10:1, more preferably in the range of 1:1 to 5:1.
[0026] In the context of the present invention, it is envisaged that the platinum group metal of the first catalyst is also supported on the oxygen storage component.
[0027] Preferably, the coating of the first catalyst further comprises a non-zeolitic oxide material, which non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably comprises zirconia.
[0028] Preferably, the coating of the first catalyst comprises non-zeolitic oxide material in an amount in the range of 0.5 wt.-% to 12 wt.-%, more preferably in the range of 1 wt.-% to 10 wt.-%, more preferably in the range of 1 wt.-% to 5 wt.-%, calculated as oxide, based on the weight of the coating of the first catalyst.
[0029] Preferably, the coating of the first catalyst further comprises an oxide of an alkaline earth metal, more preferably the alkaline earth metal is selected from the group consisting of barium, strontium and magnesium, more preferably selected from the group consisting of barium and strontium, more preferably barium.
[0030] Preferably, the coating of the first catalyst comprises an alkaline earth metal oxide in an amount in the range of 0.5 wt. % to 15 wt. %, more preferably in the range of 1 wt. % to 10 wt. %, more preferably in the range of 1 wt. % to 6 wt. %, based on the weight of the coating of the first catalyst.
[0031] Preferably, the coating of the first catalyst comprises a platinum group metal component supported on a porous oxidic material, more preferably an oxygen storage component as defined above, more preferably a non-zeolitic oxidic material as defined above, and more preferably an alkaline earth metal oxide as defined above.
[0032] Preferably, 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the coating of the first catalyst consists of a platinum group metal component supported on a porous oxidic material, more preferably an oxygen storage component as defined above, more preferably a non-zeolitic oxidic material as defined above, and more preferably an alkaline earth metal oxide as defined above. More preferably, the coating of the first catalyst consists of a platinum group metal component supported on a porous oxidic material, more preferably an oxygen storage component as defined above, more preferably a non-zeolitic oxidic material as defined above, and more preferably an alkaline earth metal oxide as defined above.
[0033] Preferably, the substrate of the first catalyst is a flow-through substrate, more preferably a ceramic flow-through substrate.
[0034] Preferably, the ceramic substrate is made of any suitable refractory material, such as cordierite, cordierite-α-alumina, aluminum titanate, silicon titanate, silicon carbide, silicon nitride, zircon mullite, spodumene, alumina-silica-magnesium, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, α-alumina, aluminosilicate, etc.
[0035] Preferably, the first catalyst consists of a substrate and a coating.
[0036] Preferably, the coating of the first catalyst extends over more than 98% to 100%, more preferably over more than 99% to 100%, more preferably over more than 99.5% to 100% of the axial length of the substrate.The coating is preferably provided on the substrate of the first catalyst.
[0037] Preferably, the first catalyst comprises a loading of 1 g / in 3 Up to 7g / in 3 In the range of 1.5 g / in 3 Up to 5g / in 3 In the range of 2 g / in 3 Up to 3.5g / in3 range of coatings.
[0038] Second catalyst
[0039] Preferably, the platinum group metal component of the washcoat of the second catalyst comprises one or more of Pd, Rh and Pt, more preferably one or more of Pd and Rh, more preferably Pd and Rh.
[0040] Preferably, the coating of the second catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 100g / ft 3 In the range of 3 g / ft 3 Up to 80g / ft 3 In the range of 4 g / ft 3 Up to 50g / ft 3 The platinum group metal component is within the range.
[0041] Preferably, the porous oxide material of the platinum group metal component of the coating layer supporting the second catalyst is selected from the group consisting of alumina, ceria, silica, zirconia, titania, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of alumina, titania, zirconia, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of alumina, zirconia, a mixture of two of them and a mixed oxide of two of them, more preferably alumina.
[0042] Preferably, the second catalyst contains 0.5 g / in 3 Up to 2.5g / in 3 In the range of 0.6 g / in 3 Up to 2.0g / in 3 In the range of 0.7 g / in 3 Up to 1.5g / in 3 In the range of 0.8 g / in 3 Up to 1.2g / in 3 A range of porous oxide materials for coatings.
[0043] Preferably, the coating of the second catalyst further comprises an oxygen storage component (OSC), which oxygen storage component more preferably comprises cerium, more preferably comprises one or more of cerium oxide, a mixture of oxides including cerium oxide and a mixed oxide comprising cerium, wherein the mixed oxide comprising cerium more preferably further comprises one or more of zirconium, yttrium, neodymium, lanthanum, hafnium, samarium and praseodymium, more preferably one or more of zirconium, yttrium, neodymium, lanthanum and praseodymium, more preferably zirconium.
[0044] Preferably, the oxygen storage component of the coating of the second catalyst comprises a mixed oxide comprising cerium and zirconium.
[0045] Preferably, 95% to 100% by weight, more preferably 98% to 100% by weight, more preferably 99% to 100% by weight, more preferably 99.5% to 100% by weight of the oxygen storage component consists of a mixed oxide containing cerium and zirconium.
[0046] Preferably 10 to 60 wt %, more preferably 20 to 60 wt %, more preferably 20 to 50 wt % of the oxygen storage component consists of cerium calculated as CeO2, and more preferably 20 to 90 wt %, more preferably 40 to 70 wt %, more preferably 50 to 70 wt % of the oxygen storage component consists of zirconium calculated as ZrO2. Preferably 0 to 20 wt %, more preferably 0 to 10 wt % of the OSC consists of lanthanum and yttrium calculated as La2O3 and Y2O3. More preferably, the OSC comprises lanthanum and yttrium in addition to cerium and zirconium.
[0047] Preferably, the coating of the second catalyst comprises a loading of 1.5 g / in 3 Up to 2.5g / in 3 More preferably, it is within the range of 1.2 g / in 3 Up to 2.2g / in 3 In the range of 1.0 g / in 3 Up to 2.0g / in 3 In the range of 1 g / in 3 Up to 1.75g / in 3 Oxygen storage components within the range.
[0048] Preferably, in the coating of the second catalyst, the weight ratio of the porous oxidic material as defined above to the oxygen storage component is in the range of 1:1 to 0.5:1, more preferably in the range of 1:1 to 0.25:1.
[0049] In the context of the present invention, it is envisaged that the platinum group metal of the first catalyst is also supported on the oxygen storage component.
[0050] Preferably, the coating of the second catalyst further comprises a non-zeolitic oxide material, which non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably comprises zirconia.
[0051] Preferably, the coating of the second catalyst comprises non-zeolitic oxide material in an amount in the range of 0.5 wt.-% to 12 wt.-%, more preferably in the range of 1 wt.-% to 10 wt.-%, more preferably in the range of 1 wt.-% to 5 wt.-%, calculated as oxide, based on the weight of the coating of the first catalyst.
[0052] Preferably, the coating of the second catalyst further comprises an oxide of an alkaline earth metal, more preferably the alkaline earth metal is selected from the group consisting of barium, strontium and magnesium, more preferably selected from the group consisting of barium and strontium, more preferably barium.
[0053] Preferably, the coating of the second catalyst comprises an alkaline earth metal oxide in an amount in the range of 0.5 wt. % to 15 wt. %, more preferably in the range of 1 wt. % to 10 wt. %, more preferably in the range of 1 wt. % to 6 wt. %, based on the weight of the coating of the first catalyst.
[0054] Preferably, the coating of the second catalyst consists of a platinum group metal component supported on a porous oxidic material, more preferably an oxygen storage component as defined above, more preferably a non-zeolitic oxidic material as defined above, and more preferably an alkaline earth metal oxide as defined above.
[0055] Preferably, 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the coating of the second catalyst consists of a platinum group metal component supported on a porous oxidic material, more preferably an oxygen storage component as defined above, more preferably a non-zeolitic oxidic material as defined above, and more preferably an alkaline earth metal oxide as defined above. More preferably, the coating of the second catalyst consists of a platinum group metal component supported on a porous oxidic material, more preferably an oxygen storage component as defined above, more preferably a non-zeolitic oxidic material as defined above, and more preferably an alkaline earth metal oxide as defined above.
[0056] Preferably, the substrate of the second catalyst is a ceramic wall flow filter substrate.
[0057] Preferably, the ceramic substrate is made of any suitable refractory material, such as cordierite, cordierite-α-alumina, aluminum titanate, silicon titanate, silicon carbide, silicon nitride, zircon mullite, spodumene, alumina-silica-magnesium, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, α-alumina, aluminosilicate, etc.
[0058] Preferably, the second catalyst consists of a substrate and a coating.
[0059] Preferably, the coating of the second catalyst extends over more than 98% to 100%, preferably over more than 99% to 100%, more preferably over more than 99.5% to 100% of the axial length of the substrate.The coating is preferably provided on the substrate of the second catalyst.
[0060] Preferably, the second catalyst comprises a loading of 0.5 g / in 3 Up to 3g / in 3 In the range of 0.75 g / in 3 Up to 2.5g / in 3 In the range of 1.0 g / in 3 Up to 1.75g / in 3 range of coatings.
[0061] Preferably, there is no catalyst between the first catalyst according to (i) and the second catalyst according to (ii). In fact, it is preferred that there is no other catalyst between the three-way conversion catalyst according to (i) and the four-way conversion catalyst according to (ii).
[0062] The third catalyst
[0063] Preferably, the zeolite material contained in the SCR coating of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material more preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU. More preferably, the 12-membered ring pore zeolite material contained in the SCR coating of the third catalyst has a framework type BEA.
[0064] Preferably, the zeolite material contained in the SCR coating of the third catalyst is a 12-membered ring pore zeolite material, the zeolite material contains Fe, wherein the 12-membered ring pore zeolite material more preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU. More preferably, the 12-membered ring pore zeolite material contained in the SCR coating of the third catalyst has a framework type BEA.
[0065] Preferably, 95 wt% to 100 wt%, more preferably 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt% of the framework structure of the 12-membered ring pore zeolite material contained in the SCR coating of the third catalyst is composed of Si, Al and O, wherein in the framework structure, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1.
[0066] Preferably, the zeolite material contained in the SCR coating of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3, based on the total weight of the zeolite material, is more preferably in the range of 0.1 wt.% to 10.0 wt.%, more preferably in the range of 0.5 wt.% to 8 wt.%, more preferably in the range of 1.5 wt.% to 7.5 wt.%.
[0067] Preferably, the zeolitic material is free of Cu.
[0068] Preferably, the SCR coating of the third catalyst further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica.
[0069] Preferably, the SCR coating of the third catalyst contains non-zeolitic oxide material in an amount in the range of 0.5 wt. % to 12 wt. %, more preferably in the range of 1 wt. % to 10 wt. %, more preferably in the range of 1 wt. % to 6 wt. %, calculated as oxide, based on the weight of the SCR coating of the third catalyst.
[0070] Preferably, at most 0.00001 wt% of the SCR coating of the third catalyst consists of platinum group metals, wherein more preferably 0 wt% to 0.00001 wt% of the SCR coating of the third catalyst consists of platinum group metals.
[0071] In other words, preferably, the coating of the third catalyst is substantially free of platinum group metals, more preferably free of platinum group metals.
[0072] Preferably, the substrate of the third catalyst is a flow-through substrate, more preferably a ceramic flow-through substrate.
[0073] Preferably, the ceramic substrate is made of any suitable refractory material, such as cordierite, cordierite-α-alumina, aluminum titanate, silicon titanate, silicon carbide, silicon nitride, zircon mullite, spodumene, alumina-silica-magnesium, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, α-alumina, aluminosilicate, etc.
[0074] Preferably, 98 wt.% to 100 wt.%, more preferably 99 wt.% to 100 wt.%, more preferably 99.5 wt.% to 100 wt.%, more preferably 99.9 wt.% to 100 wt.% of the SCR coating of the third catalyst consists of zeolitic material comprising one or more of Fe and Cu, and more preferably of non-zeolitic oxidic material as defined above.
[0075] -Third catalyst: SCR catalyst
[0076] Preferably, the third catalyst consists of a substrate and an SCR coating.
[0077] Preferably, the SCR coating of the third catalyst extends over more than 98% to 100%, more preferably over more than 99% to 100%, more preferably over more than 99.5% to 100% of the axial length of the substrate.The SCR coating is preferably provided on the substrate of the third catalyst.
[0078] Preferably, the SCR coating comprises, more preferably consists of, a zeolitic material, more preferably of framework type BEA, comprising iron and a non-zeolitic oxide material, more preferably zirconium oxide.
[0079] -Third catalyst: SCR / AMOx layered catalyst
[0080] Preferably, the third catalyst comprises an ammonia oxidation catalyst (AMOx) coating in addition to the SCR coating.
[0081] a) SCR coating
[0082] Preferably, the SCR coating of the third catalyst is as defined above.
[0083] Preferably, the SCR coating of the third catalyst comprises, more preferably consists of, a zeolitic material, more preferably of framework type BEA, comprising iron and a non-zeolitic oxide material, more preferably ceria.
[0084] The proportions of the components of the SCR coating are preferably the same as those defined above for the third catalyst.
[0085] b) AMOx coating
[0086] Preferably, the AMOx coating of the third catalyst comprises a platinum group metal, more preferably one or more of Pt, Pd and Rh, more preferably one or more of Pt and Pd, more preferably Pt.
[0087] Preferably, the AMOx coating of the third catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 20g / ft 3 In the range of 2 g / ft 3 Up to 10g / ft 3 In the range of 3 g / ft 3 Up to 5g / ft 3 within the range of platinum group metals.
[0088] Preferably, the AMOx coating of the third catalyst comprises a porous oxidic material, more preferably for supporting a platinum group metal as defined above, more preferably platinum.
[0089] Preferably, the porous oxidic material is selected from the group consisting of titania, alumina, ceria, silica, zirconia, a mixture of two or more thereof and a mixed oxide of two or more thereof, preferably selected from the group consisting of titania, alumina and silica, more preferably titania.
[0090] Preferably, the AMOx coating of the third catalyst contains 0.25 g / in 3 Up to 3g / in 3 In the range of 0.5 g / in 3 Up to 1.5g / in 3 Porous oxide materials within a range of.
[0091] Preferably, the AMOx coating of the third catalyst (further) comprises a zeolite material containing one or more of Fe and Cu, more preferably a zeolite material containing Fe.
[0092] Preferably, the zeolite material of the AMOx coating of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material more preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU. More preferably, the zeolite material of the AMOx coating of the third catalyst is a zeolite material having a framework type BEA.
[0093] Preferably, 95 wt % to 100 wt %, more preferably 98 wt % to 100 wt %, more preferably 99 wt % to 100 wt %, more preferably 99.5 wt % to 100 wt % of the framework type of the 12-membered ring pore zeolite material contained in the AMOx coating of the third catalyst is composed of Si, Al and O.
[0094] Preferably, in the framework structure of the zeolitic material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1.
[0095] Preferably, the zeolite material contained in the AMOx coating of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3, based on the total weight of the zeolite material, is more preferably in the range of 0.1 wt.% to 15.0 wt.%, more preferably in the range of 0.5 wt.% to 10.0 wt.%, more preferably in the range of 1.5 wt.% to 7.5 wt.%.
[0096] Preferably, in the AMOx coating, the weight ratio of the zeolite material comprising one or more of Fe and Cu to the porous oxidic material as defined above is in the range of 0.5:1 to 2:1, preferably in the range of 0.75:1 to 1.5:1, more preferably in the range of 1:1 to 1.25:1.
[0097] Preferably, the AMOx coating further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably silica.
[0098] Preferably, the coating of the third catalyst comprises non-zeolitic oxide material in an amount in the range of 0.5 wt. % to 18 wt. %, more preferably in the range of 5 wt. % to 16 wt. %, more preferably in the range of 8 wt. % to 13 wt. %, calculated as oxide, based on the weight of the AMOx coating of the third catalyst.
[0099] Preferably, the AMOx coating of the third catalyst comprises a platinum group metal as defined above, a porous oxide material loaded with a platinum group metal as defined above, a zeolite material comprising one or more of Fe and Cu as defined in any one of the above, and preferably a non-zeolitic oxide material as defined above.
[0100] Preferably, 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the AMOx coating of the third catalyst consists of a platinum group metal as defined above, a porous oxidic material loaded with a platinum group metal as defined above, a zeolite material comprising one or more of Fe and Cu as defined in any one of the above, and preferably a non-zeolite oxidic material as defined above. More preferably, the AMOx coating of the third catalyst consists of a platinum group metal as defined above, a porous oxidic material loaded with a platinum group metal as defined above, a zeolite material comprising one or more of Fe and Cu as defined in any one of the above, and preferably a non-zeolite oxidic material as defined above.
[0101] Preferably, the AMOx coating is disposed on the substrate of the third catalyst over more than 98% to 100%, preferably 99% to 100%, more preferably 99.5% to 100% of the axial length of the substrate, and the SCR coating is disposed on the AMOx coating over more than 98% to 100%, preferably 99% to 100%, more preferably 99.5% to 100% of the axial length of the substrate.
[0102] -Third catalyst: SCR / AMOx regionalized catalyst
[0103] Preferably, the third catalyst comprises an inlet zone and an outlet zone, the inlet zone comprising the SCR coating, more preferably consisting of the SCR coating, and the outlet zone comprising an ammonia oxidation catalyst coating, more preferably consisting of an ammonia oxidation catalyst coating.
[0104] Preferably, the inlet zone extends from the inlet end of the substrate towards the outlet end by more than x% of the axial length of the substrate, wherein x is in the range of 20 to 60, more preferably in the range of 30 to 55, more preferably in the range of 45 to 55.
[0105] Preferably, the outlet zone extends from the outlet end of the substrate towards the inlet end by more than y% of the axial length of the substrate, where y=100-x.
[0106] Preferably, the SCR coating is disposed on the substrate of the third catalyst over more than 50% of the axial length of the substrate, thereby forming an inlet zone. Preferably, the AMOx coating is disposed on the substrate of the third catalyst over more than 50% of the axial length of the substrate.
[0107] a) Inlet area: SCR coating
[0108] Preferably, the SCR coating of the inlet zone comprises, more preferably consists of, a zeolitic material, more preferably of framework type BEA, comprising iron and a non-zeolitic oxidic material, more preferably the non-zeolitic material is a mixture of silica and alumina.
[0109] The components and proportions of the SCR coating are preferably as defined above.
[0110] b) Exit area: AMOx coating
[0111] Preferably, the AMOx coating of the outlet zone comprises:
[0112] - a first coating comprising a platinum group metal and a zeolite material comprising one or more of Fe and Cu supported on a porous oxidic material;
[0113] - a second coating comprising a zeolitic material containing one or more of Fe and Cu, wherein at most 0.0001 wt. % of the first coating consists of platinum group metals;
[0114] wherein the first coating is disposed on the substrate at a length exceeding the exit zone, and the second coating is disposed on the first coating at a length exceeding the exit zone;
[0115] or
[0116] wherein the second coating is disposed on the substrate over the length exceeding the exit zone,
[0117] And the first coating is disposed on the second coating over the length exceeding the exit zone.
[0118] Preferably, the first coating is disposed on the substrate over the length exceeding the exit zone, and the second coating is disposed on the first coating over the length exceeding the exit zone.
[0119] Preferably, the zeolite material of the second coating layer of the AMOx coating layer of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material more preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the AMOx coating layer of the third catalyst has a framework type BEA.
[0120] Preferably, 95 wt% to 100 wt%, more preferably 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt% of the framework type of the 12-membered ring pore zeolite material contained in the second coating layer of the AMOx coating layer of the third catalyst is composed of Si, Al and O.
[0121] Preferably, in the framework structure of the zeolitic material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1.
[0122] Preferably, the zeolite material contained in the second coating layer of the AMOx coating layer of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3, based on the total weight of the zeolite material, is more preferably in the range of 0.1 wt.% to 15.0 wt.%, more preferably in the range of 1.0 wt.% to 10.0 wt.%, more preferably in the range of 3.0 wt.% to 7.5 wt.%.
[0123] Preferably, at most 0.00001 wt% of the second coating layer of the AMOx coating layer of the third catalyst consists of a platinum metal component, wherein more preferably 0 wt% to 0.00001 wt% of the second coating layer of the AMOx coating layer of the third catalyst consists of a platinum group metal component.
[0124] In other words, it is preferred that the second coating layer of the AMOx coating layer of the third catalyst is substantially free of platinum group metals, and more preferably free of platinum group metals.
[0125] Preferably, the second coating layer of the AMOx coating layer of the third catalyst further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably ceria.
[0126] Preferably, the second coating layer of the AMOx coating of the third catalyst comprises a non-zeolitic oxide material, more preferably ceria, in an amount calculated as an oxide in the range of 0.5 wt. % to 12 wt. %, more preferably in the range of 1 wt. % to 10 wt. %, more preferably in the range of 1 wt. % to 6 wt. %, more preferably in the range of 1 wt. % to 4 wt. %.
[0127] Preferably, the second coating of the AMOx coating of the third catalyst comprises a zeolitic material comprising one or more of Fe and Cu, and more preferably comprises a non-zeolitic oxidic material as defined hereinbefore.
[0128] Preferably, 98 wt% to 100 wt%, preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the second coating of the AMOx coating of the third catalyst consists of a zeolite material comprising one or more of Fe and Cu, and more preferably a non-zeolitic oxidic material as defined above. More preferably, the second coating of the AMOx coating of the third catalyst consists of a zeolite material comprising one or more of Fe and Cu; and more preferably a non-zeolitic oxidic material as defined above.
[0129] Preferably, the platinum group metal contained in the first coating layer of the AMOx coating layer of the third catalyst is one or more of Pt, Pd and Rh, more preferably one or more of Pt and Pd, more preferably Pt.
[0130] Preferably, the first coating of the AMOx coating of the third catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 20g / ft 3 In the range of 2 g / ft 3 Up to 10g / ft 3 In the range of 3 g / ft 3 Up to 7.5g / ft 3 within the range of platinum group metals.
[0131] Preferably, the porous oxidic material of the first coating layer of the AMOx coating layer of the third catalyst is selected from the group consisting of titania, alumina, ceria, silica, zirconia, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of titania, silica and alumina, more preferably titania.
[0132] Preferably, the first coating layer of the AMOx coating of the third catalyst contains the porous oxidic material in an amount in the range of 10 wt % to 80 wt %, more preferably in the range of 30 wt % to 70 wt %, more preferably in the range of 45 wt % to 55 wt %, based on the weight of the first coating layer of the AMOx coating of the third catalyst.
[0133] Preferably, the zeolite material of the first coating layer of the AMOx coating layer of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material more preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the second coating layer of the AMOx coating layer of the third catalyst has a framework type BEA.
[0134] Preferably, 95 wt% to 100 wt%, more preferably 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt% of the framework type of the 12-membered ring pore zeolite material contained in the first coating layer of the AMOx coating layer of the third catalyst is composed of Si, Al and O.
[0135] Preferably, in the framework structure of the zeolite material of the first coating, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1.
[0136] Preferably, the zeolite material contained in the first coating layer of the AMOx coating layer of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3, based on the total weight of the zeolite material, is more preferably in the range of 1.0 wt.% to 15.0 wt.%, more preferably in the range of 2.0 wt.% to 10.0 wt.%, more preferably in the range of 3.0 wt.% to 7.5 wt.%.
[0137] Preferably, in the first coating layer of the AMOx coating layer of the third catalyst, the weight ratio of the zeolite material containing one or more of Fe and Cu to the porous oxidic material is in the range of 0.25:1 to 2:1, more preferably in the range of 0.5:1 to 1:1.
[0138] Preferably, the first coating layer of the AMOx coating layer of the third catalyst further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and titania, more preferably silica.
[0139] Preferably, the first coating layer of the AMOx coating of the third catalyst contains non-zeolitic oxide material in an amount in the range of 0.5 wt. % to 18 wt. %, more preferably in the range of 5 wt. % to 16 wt. %, more preferably in the range of 8 wt. % to 13 wt. %, calculated as oxide, based on the weight of the first coating layer of the AMOx coating of the third catalyst.
[0140] Preferably, the first coating of the AMOx coating of the third catalyst comprises a platinum group metal supported on a porous oxide material, a zeolitic material comprising one or more of Fe and Cu, and more preferably a non-zeolitic oxide material as defined hereinbefore.
[0141] Preferably, 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the first coating layer of the AMOx coating layer of the third catalyst consists of a platinum group metal supported on a porous oxide material, a zeolite material comprising one or more of Fe and Cu, and more preferably a non-zeolite oxide material as defined above. More preferably, the first coating layer of the AMOx coating layer of the third catalyst consists of a platinum group metal supported on a porous oxide material, a zeolite material comprising one or more of Fe and Cu, and more preferably a non-zeolite oxide material as defined above.
[0142] Preferably, the AMOx coating of the third catalyst consists of a first coating and a second coating.
[0143] Preferably, the third catalyst consists of a substrate, an SCR coating and an AMOx coating.
[0144] -Third catalyst: SCR / PGM layered catalyst
[0145] Preferably, the third catalyst comprises an oxidation catalyst coating in addition to the SCR coating.
[0146] a) SCR coating
[0147] Preferably, the SCR coating of the third catalyst is as defined above.
[0148] Preferably, the SCR coating of the third catalyst comprises, more preferably consists of, a zeolitic material, more preferably of framework type BEA, comprising iron and a non-zeolitic oxidic material.
[0149] Preferably, the SCR coating of the third catalyst further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably zirconia.
[0150] Preferably, the SCR coating of the third catalyst comprises non-zeolitic material in an amount in the range of 0.5 wt. % to 12 wt. %, more preferably in the range of 1 wt. % to 10 wt. %, more preferably in the range of 1 wt. % to 6 wt. %, more preferably in the range of 2 wt. % to 5 wt. %.
[0151] The proportions of the components of the SCR coating are preferably the same as those defined above for the third catalyst.
[0152] b) Oxidation catalyst coating
[0153] Preferably, the oxidation catalyst coating of the third catalyst comprises a platinum group metal, more preferably one or more of Pt, Pd and Rh, more preferably one or more of Pt and Pd, more preferably Pt.
[0154] Preferably, the oxidation catalyst coating of the third catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 20g / ft 3 In the range of 2 g / ft 3 Up to 10g / ft 3 In the range of 3 g / ft 3 Up to 5g / ft 3 within the range of platinum group metals.
[0155] Preferably, the oxidation catalyst coating of the third catalyst comprises a porous oxidic material, more preferably for supporting a platinum group metal as defined above, more preferably platinum.
[0156] Preferably, the porous oxide material comprises oxygen and one or more of aluminum, titanium, cerium, silicon and zirconium, preferably one or more of aluminum, titanium and silicon, more preferably aluminum.
[0157] Preferably, the porous oxide material, more preferably the porous oxide material comprising oxygen and aluminum, further comprises a rare earth metal, more preferably one or more of lanthanum, yttrium, cerium, praseodymium, neodymium, more preferably lanthanum.
[0158] Preferably, 1 to 6% by weight, more preferably 2 to 5% by weight, of the porous material consists of rare earth metals calculated as oxides.
[0159] Preferably, 99 to 100 wt %, more preferably 99.5 to 100 wt %, more preferably 99.9 to 100 wt % of the porous material consists of oxygen, aluminum and a rare earth metal, preferably lanthanum.
[0160] Preferably, the oxidation catalyst coating of the third catalyst contains 0.25 g / in 3 Up to 3g / in 3 In the range of 0.75 g / in 3 Up to 2g / in 3 Porous oxide materials within a range of.
[0161] Preferably, 98% to 100% by weight, more preferably 99% to 100% by weight, more preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight of the oxidation catalyst coating of the third catalyst consists of a platinum group metal as defined above and a porous oxidic material supporting the platinum group metal as defined above. More preferably, the oxidation catalyst coating of the third catalyst consists of a platinum group metal as defined above and a porous oxidic material supporting the platinum group metal as defined above.
[0162] Preferably, the oxidation catalyst coating is disposed on the substrate of the third catalyst at more than 98% to 100%, preferably 99% to 100%, more preferably 99.5% to 100% of the axial length of the substrate, and the SCR coating is disposed on the oxidation catalyst coating at more than 98% to 100%, preferably 99% to 100%, more preferably 99.5% to 100% of the axial length of the substrate.
[0163] Preferably, at most 0.01 wt%, more preferably at most 0.001 wt% of the oxidation catalyst coating of the third catalyst consists of zeolite material, wherein more preferably 0 wt% to 0.0001 wt% of the oxidation catalyst coating of the third catalyst consists of zeolite material.
[0164] In other words, it is preferred that the second coating layer of the AMOx coating layer of the third catalyst is substantially free of platinum group metals, and more preferably free of platinum group metals.
[0165] Preferably, the third catalyst consists of a substrate, an SCR coating and an oxidation catalyst coating.
[0166] Preferably, no catalyst is present between the second catalyst according to (ii) and the third catalyst according to (iii).
[0167] The invention further relates to a method for the simultaneous selective catalytic reduction of NOx, oxidation of hydrocarbons, oxidation of nitrogen monoxide and oxidation of ammonia, the method comprising
[0168] (1) providing an exhaust gas stream from a gasoline engine, the exhaust gas stream comprising one or more of NOx, ammonia, nitrogen monoxide, and hydrocarbons;
[0169] (2) The exhaust gas flow provided in (1) is passed through the exhaust gas system according to the present invention.
[0170] The invention is further illustrated by the following set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where the scope of an embodiment is mentioned, for example in the context of a term such as "a system according to any one of embodiments 1 to 4", each embodiment within this scope is meant to be explicitly disclosed to the skilled person, i.e. the wording of this term should be understood by the skilled person as being synonymous with "a system according to any one of embodiments 1, 2, 3 and 4". In addition, it should be explicitly pointed out that the following set of embodiments represents a properly structured part of a general description of preferred aspects of the invention, and therefore properly supports but does not represent the claims of the invention.
[0171] 1. An exhaust gas treatment system for treating an exhaust gas flow leaving a gasoline engine, the exhaust gas treatment system having an upstream end for introducing the exhaust gas flow into the exhaust gas treatment system, wherein the exhaust gas treatment system comprises
[0172] (i) a first catalyst, the first catalyst being a three-way conversion catalyst having an inlet end and an outlet end and comprising a coating disposed on a substrate, wherein the coating comprises a platinum group metal component supported on a porous oxidic material;
[0173] (ii) a second catalyst that is a four-way conversion catalyst having an inlet end and an outlet end and comprising a washcoat disposed on a wall flow filter substrate, wherein the washcoat comprises a platinum group metal component supported on a porous oxidic material;
[0174] (iii) a third catalyst having an inlet end and an outlet end, wherein the third catalyst comprises a substrate and a washcoat for selective catalytic reduction of NOx, wherein the SCR washcoat comprises a zeolite material comprising one or more of Fe and Cu, wherein at most 0.0001 wt. % of the SCR washcoat consists of a platinum group metal;
[0175] wherein the first catalyst according to (i) is the first catalyst of the exhaust treatment system downstream of the upstream end of the exhaust treatment system, and wherein the inlet end of the first catalyst is arranged upstream of the outlet end of the first catalyst;
[0176] wherein in the exhaust gas treatment system, the second catalyst according to (ii) is located downstream of the first catalyst according to (i), and wherein the inlet end of the second catalyst is arranged upstream of the outlet end of the second catalyst;
[0177] Wherein in the exhaust gas treatment system, the third catalyst according to (iii) is located downstream of the second catalyst according to (ii), and wherein the inlet end of the third catalyst is arranged upstream of the outlet end of the third catalyst.
[0178] 2. An exhaust gas treatment system according to embodiment 1, wherein the outlet end of the first catalyst according to (i) is fluidly connected to the inlet end of the second catalyst according to (ii), and wherein between the outlet end of the first catalyst according to (i) and the inlet end of the second catalyst according to (ii), no catalyst for treating the exhaust gas flow leaving the first catalyst is located in the exhaust gas treatment system.
[0179] 3. An exhaust gas treatment system according to embodiment 1 or 2, wherein the outlet end of the second catalyst according to (ii) is fluidly connected to the inlet end of the third catalyst according to (iii), and wherein between the outlet end of the second catalyst according to (ii) and the inlet end of the third catalyst according to (iii), no catalyst for treating the exhaust gas flow leaving the second catalyst is located in the exhaust gas treatment system.
[0180] 4. The exhaust gas treatment system according to any one of embodiments 1 to 3, wherein the platinum group metal component of the coating of the first catalyst comprises one or more of Pd, Rh and Pt, preferably
[0181] One or more of Pd and Rh, more preferably Pd and Rh.
[0182] 5. The exhaust gas treatment system according to any one of embodiments 1 to 4, wherein the coating of the first catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 200g / ft 3 In the range of 20 g / ft 3 Up to 180g / ft 3 In the range of 50 g / ft 3 Up to 150g / ft 3 The platinum group metal component is within the range.
[0183] 6. An exhaust gas treatment system according to any one of embodiments 1 to 5, wherein the porous oxide material of the platinum group metal component of the coating layer supporting the first catalyst is selected from the group consisting of aluminum oxide, ceria, silica, zirconium oxide, titanium oxide, a mixture of two or more thereof and a mixed oxide of two or more thereof, preferably selected from the group consisting of aluminum oxide, titanium oxide, zirconium oxide, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of aluminum oxide, zirconium oxide, a mixture of two of them and a mixed oxide of two of them, more preferably aluminum oxide.
[0184] 7. An exhaust gas treatment system according to any one of embodiments 1 to 6, wherein the coating of the first catalyst further comprises an oxygen storage component, which oxygen storage component preferably comprises cerium, more preferably comprises one or more of cerium oxide, a mixture of oxides including cerium oxide, and a mixed oxide comprising cerium, wherein the mixed oxide comprising cerium more preferably further comprises one or more of zirconium, yttrium, neodymium, lanthanum, hafnium, samarium and praseodymium, more preferably one or more of zirconium, yttrium, neodymium, lanthanum and praseodymium, more preferably zirconium.
[0185] 8. The exhaust gas treatment system according to embodiment 7, wherein the oxygen storage component of the coating of the first catalyst comprises a mixed oxide comprising cerium and zirconium;
[0186] wherein preferably 95% to 100% by weight, more preferably 98% to 100% by weight, more preferably 99% to 100% by weight, more preferably 99.5% to 100% by weight of the oxygen storage component consists of a mixed oxide containing cerium and zirconium;
[0187] wherein more preferably 10 wt % to 60 wt %, more preferably 20 wt % to 60 wt %, more preferably 20 wt % to 50 wt % of the oxygen storage component consists of cerium calculated as CeO2, and more preferably 20 wt % to 90 wt %, more preferably 40 wt % to 70 wt %, more preferably 50 wt % to 70 wt % of the oxygen storage component consists of zirconium calculated as ZrO2; wherein more preferably 0 wt % to 20 wt %, more preferably 0 wt % to 10 wt % of the OSC consists of lanthanum and yttrium calculated as La2O3 and Y2O3.
[0188] 9. The exhaust gas treatment system according to embodiment 7 or 8, wherein the coating of the first catalyst comprises a loading of 0.3 g / in 3 Up to 5g / in 3 In the range of 0.4 g / in 3 Up to 3.5g / in 3 In the range of 0.45 g / in 3Up to 3.0g / in 3 In the range of 0.5 g / in 3 Up to 2.5g / in 3 Oxygen storage components within the range.
[0189] 10. An exhaust gas treatment system according to any one of embodiments 1 to 9, wherein, in the coating of the first catalyst, the weight ratio of the porous oxidizing material as defined in any one of embodiments 7 to 9 to the oxygen storage component is in the range of 1:1 to 10:1, preferably in the range of 1:1 to 5:1.
[0190] 11. An exhaust gas treatment system according to any one of embodiments 1 to 10, wherein the coating of the first catalyst further comprises a non-zeolitic oxide material, which non-zeolitic oxide material preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably comprises zirconia.
[0191] 12. An exhaust gas treatment system according to embodiment 11, wherein the coating of the first catalyst contains a non-zeolitic oxidic material in an amount calculated as an oxide in the range of 0.5 wt. % to 12 wt. %, preferably in the range of 1 wt. % to 10 wt. %, and more preferably in the range of 1 wt. % to 5 wt. %, based on the weight of the coating of the first catalyst.
[0192] 13. An exhaust gas treatment system according to any one of embodiments 1 to 12, wherein the coating of the first catalyst further comprises an oxide of an alkaline earth metal, the alkaline earth metal is preferably selected from the group consisting of barium, strontium and magnesium, more preferably selected from the group consisting of barium and strontium, more preferably barium.
[0193] 14. An exhaust gas treatment system according to embodiment 13, wherein based on the weight of the coating of the first catalyst, the coating of the first catalyst contains an alkaline earth metal oxide in an amount ranging from 0.5 wt.% to 15 wt.%, preferably in a range of 1 wt.% to 10 wt.%, and more preferably in a range of 1 wt.% to 6 wt.%.
[0194] 15. An exhaust gas treatment system according to any one of embodiments 1 to 14, wherein preferably 98 wt % to 100 wt %, preferably 99 wt % to 100 wt %, more preferably 99.5 wt % to 100 wt %, more preferably 99.9 wt % of the coating of the first catalyst
[0195] To 100 wt. % consists of a platinum group metal component supported on a porous oxidic material, preferably an oxygen storage component as defined in any one of Embodiments 7 to 9, more preferably a non-zeolitic oxidic material as defined in Embodiment 11 or 12, and more preferably an alkaline earth metal oxide as defined in Embodiment 13 or 14.
[0196] 16. The exhaust gas treatment system according to any one of embodiments 1 to 15, wherein the substrate of the first catalyst is a flow-through substrate, preferably a ceramic flow-through substrate.
[0197] 17. The exhaust gas treatment system according to any one of embodiments 1 to 16, wherein the first catalyst consists of a substrate and a coating.
[0198] 18. The exhaust gas treatment system according to any one of embodiments 1 to 17, wherein the platinum group metal component of the coating of the second catalyst comprises one or more of Pd, Rh and Pt, preferably one or more of Pd and Rh, more preferably Pd and Rh;
[0199] The coating of the second catalyst preferably comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 100g / ft 3 In the range of 3 g / ft 3 Up to 80g / ft 3 In the range of 4 g / ft 3 Up to 50g / ft 3 The platinum group metal component is within the range.
[0200] 19. An exhaust gas treatment system according to any one of embodiments 1 to 18, wherein the porous oxide material of the platinum group metal component of the coating layer supporting the second catalyst is selected from the group consisting of aluminum oxide, ceria, silica, zirconium oxide, titanium oxide, a mixture of two or more thereof and a mixed oxide of two or more thereof, preferably selected from the group consisting of aluminum oxide, titanium oxide, zirconium oxide, a mixture of two or more thereof and a mixed oxide of two or more thereof, more preferably selected from the group consisting of aluminum oxide, zirconium oxide, a mixture of two of them and a mixed oxide of two of them, more preferably aluminum oxide.
[0201] 20. The exhaust gas treatment system according to any one of embodiments 1 to 19, wherein the coating of the second catalyst further comprises an oxygen storage component (OSC), the oxygen storage component preferably comprising cerium, more preferably comprising one or more of cerium oxide, a mixture of oxides including cerium oxide, and a mixed oxide comprising cerium, wherein the mixed oxide comprising cerium more preferably further comprises one or more of zirconium, yttrium, neodymium, lanthanum, hafnium, samarium and praseodymium, more preferably one or more of zirconium, yttrium, neodymium, lanthanum and praseodymium, more preferably zirconium;
[0202] wherein the oxygen storage component of the coating of the second catalyst preferably comprises a mixed oxide containing cerium and zirconium;
[0203] wherein more preferably 95 wt % to 100 wt %, more preferably 98 wt % to 100 wt %, more preferably 99 wt % to 100 wt %, more preferably 99.5 wt % to 100 wt % of the oxygen storage component consists of a mixed oxide containing cerium and zirconium;
[0204] wherein more preferably 10 wt % to 60 wt %, more preferably 20 wt % to 60 wt %, more preferably 20 wt % to 50 wt % of the oxygen storage component consists of cerium calculated as CeO2, and more preferably 20 wt % to 90 wt %, more preferably 40 wt % to 70 wt %, more preferably 50 wt % to 70 wt % of the oxygen storage component consists of cerium calculated as CeO2.
[0205] wherein more preferably 0 wt % to 20 wt %, more preferably 0 wt % to 10 wt % of the OSC consists of lanthanum and yttrium calculated as La 2 O 3 and Y 2 O 3 .
[0206] 21. The exhaust gas treatment system according to embodiment 19 or 20, wherein the coating of the second catalyst comprises a loading of 1.5 g / in 3 Up to 2.5g / in 3 In the range of 1.2 g / in 3 to
[0207] 2.2g / in 3 In the range of 1.0 g / in 3 Up to 2.0g / in 3 In the range of 1 g / in 3 Up to 1.75g / in 3 Oxygen storage components within the range.
[0208] 22. An exhaust gas treatment system according to any one of embodiments 1 to 21, wherein, in the coating of the second catalyst, the weight ratio of the porous oxidizing material as defined in any one of embodiments 17 to 19 to the oxygen storage component is in the range of 1:1 to 0.5:1, preferably in the range of 1:1 to 0.25:1.
[0209] 23. An exhaust gas treatment system according to any one of embodiments 1 to 22, wherein the coating of the second catalyst further comprises a non-zeolitic oxidic material, the non-zeolitic oxidic material preferably comprising one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprising one or more of zirconia, alumina, ceria and silica, more preferably comprising zirconia;
[0210] Wherein the coating of the second catalyst preferably comprises non-zeolitic oxide material in an amount in the range of 0.5 wt. % to 12 wt. %, more preferably in the range of 1 wt. % to 10 wt. %, more preferably in the range of 1 wt. % to 5 wt. %, calculated as oxide, based on the weight of the coating of the first catalyst.
[0211] 24. The exhaust gas treatment system according to any one of embodiments 1 to 23, wherein the coating of the second catalyst further comprises an oxide of an alkaline earth metal, the alkaline earth metal is preferably selected from the group consisting of barium, strontium and magnesium, more preferably selected from the group consisting of barium and strontium, more preferably barium;
[0212] Wherein the coating layer of the second catalyst preferably comprises an alkaline earth metal oxide in an amount in the range of 0.5 wt % to 15 wt %, preferably in the range of 1 wt % to 10 wt %, more preferably in the range of 1 wt % to 6 wt %, based on the weight of the coating layer of the first catalyst.
[0213] 25. An exhaust gas treatment system according to any one of embodiments 1 to 24, wherein preferably 98 wt% to 100 wt%, preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the coating of the second catalyst consists of a platinum group metal component supported on a porous oxide material, preferably an oxygen storage component as defined in any one of embodiments 20 to 22, more preferably a non-zeolitic oxide material as defined in embodiment 23, and more preferably an alkaline earth metal oxide as defined in embodiment 24.
[0214] 26. The exhaust treatment system according to any one of embodiments 1 to 25, wherein the substrate of the second catalyst is a ceramic wall flow filter substrate.
[0215] 27. The exhaust gas treatment system according to any one of embodiments 1 to 26, wherein the second catalyst consists of a substrate and a coating.
[0216] 28. An exhaust gas treatment system according to any one of embodiments 1 to 27, wherein the zeolite material contained in the SCR coating of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the SCR coating of the third catalyst has a framework type BEA;
[0217] Preferably, the zeolite material contained in the SCR coating of the third catalyst contains Fe.
[0218] 29. An exhaust gas treatment system according to any one of embodiments 1 to 28, wherein 95 wt% to 100 wt%, preferably 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt% of the framework structure of the 12-membered ring pore zeolite material contained in the SCR coating of the third catalyst is composed of Si, Al and O, wherein in the framework structure, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 10:1.
[0219] In the range of 15:1.
[0220] 30. An exhaust gas treatment system according to any one of embodiments 1 to 29, wherein the zeolite material contained in the SCR coating of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3 based on the total weight of the zeolite material is preferably in the range of 0.1 wt.% to 10.0 wt.%, more preferably in the range of 0.5 wt.% to 8 wt.%, more preferably in the range of 1.5 wt.% to 7.5 wt.%.
[0221] 31. An exhaust gas treatment system according to any one of embodiments 1 to 26, wherein the SCR coating of the third catalyst further comprises a non-zeolite oxide material, wherein the non-zeolite oxide material preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica.
[0222] 32. An exhaust gas treatment system according to embodiment 31, wherein the SCR coating of the third catalyst contains a non-zeolitic oxidizing material in an amount calculated as an oxide in the range of 0.5 wt.% to 12 wt.%, preferably in the range of 1 wt.% to 10 wt.%, and more preferably in the range of 1 wt.% to 6 wt.%, based on the weight of the SCR coating of the third catalyst.
[0223] 33. An exhaust gas treatment system according to any one of embodiments 1 to 32, wherein at most 0.00001 wt.% of the SCR coating of the third catalyst consists of platinum group metals, wherein preferably 0 wt.% to 0.00001 wt.% of the SCR coating of the third catalyst consists of platinum group metals.
[0224] 34. The exhaust gas treatment system according to any one of embodiments 1 to 33, wherein the substrate of the third catalyst is a flow-through substrate, preferably a ceramic flow-through substrate.
[0225] 35. An exhaust gas treatment system according to any one of embodiments 1 to 34, wherein 98 wt.% to 100 wt.%, preferably 99 wt.% to 100 wt.%, more preferably 99.5 wt.% to 100 wt.%, more preferably 99.9 wt.% to 100 wt.% of the SCR coating of the third catalyst consists of a zeolite material comprising one or more of Fe and Cu, and preferably consists of a non-zeolitic oxidic material as defined in embodiment 31 or 32.
[0226] 36. The exhaust gas treatment system according to any one of embodiments 1 to 35, wherein the third catalyst consists of a substrate and an SCR coating.
[0227] 37. The exhaust gas treatment system according to embodiment 36, wherein the SCR coating comprises, preferably consists of, a zeolite material, the zeolite material preferably having a framework type
[0228] BEA, comprising iron and a non-zeolitic oxide material, preferably zirconium oxide.
[0229] 38. An exhaust gas treatment system according to any one of embodiments 1 to 37, wherein the SCR
[0230] In addition to the coating, the third catalyst also includes an ammonia oxidation catalyst (AMOx) coating.
[0231] 39. The exhaust gas treatment system according to embodiment 38, wherein the SCR coating of the third catalyst comprises a zeolite material, preferably consists of a zeolite material, and the zeolite material is preferably
[0232] It has a framework type BEA, comprising iron and a non-zeolitic oxide material, preferably ceria.
[0233] 40. The exhaust treatment system according to embodiment 38 or 39, wherein the AMOx coating of the third catalyst comprises a platinum group metal, preferably one or more of Pt, Pd and Rh, more preferably one or more of Pt and Pd, more preferably Pt.
[0234] 41. The exhaust gas treatment system of embodiment 40, wherein the AMOx coating of the third catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 20g / ft 3 In the range of 2g / ft 3 Up to 10g / ft 3 In the range of 3 g / ft 3 Up to 5g / ft 3 within the range of platinum group metals.
[0235] 42. An exhaust gas treatment system according to any one of embodiments 38 to 41, wherein the AMOx coating of the third catalyst comprises a porous oxide material, preferably for supporting a platinum group metal as defined in embodiment 40 or 41, wherein the porous oxide material is selected from the group consisting of titanium dioxide, aluminum oxide, cerium dioxide, silicon dioxide, zirconium oxide, a mixture of two or more thereof, and a mixed oxide of two or more thereof, preferably selected from the group consisting of titanium dioxide, aluminum oxide and silicon dioxide, more preferably titanium dioxide.
[0236] 43. The exhaust gas treatment system according to embodiment 42, wherein the AMOx coating of the third catalyst comprises an amount of 0.25 g / in 3 Up to 3g / in 3 In the range of 0.5 g / in 3 Up to 1.5g / in 3 Porous oxide materials within a range of.
[0237] 44. An exhaust gas treatment system according to any one of embodiments 38 to 43, wherein the AMOx coating of the third catalyst (further) comprises a zeolite material containing one or more of Fe and Cu, preferably a zeolite material containing Fe.
[0238] 45. An exhaust gas treatment system according to embodiment 44, wherein the zeolite material of the AMOx coating of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the AMOx coating of the third catalyst has a framework type BEA.
[0239] 46. The exhaust gas treatment system according to embodiment 45, wherein 95 wt% of the framework structure of the 12-membered ring pore zeolite material contained in the AMOx coating of the third catalyst
[0240] To 100 wt. %, preferably 98 wt. % to 100 wt. %, more preferably 99 wt. % to 100 wt. %, more preferably 99.5 wt. % to 100 wt. % consists of Si, Al and O, wherein in the framework structure, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1.
[0241] 47. An exhaust gas treatment system according to any one of embodiments 44 to 46, wherein the zeolite material contained in the AMOx coating of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3 based on the total weight of the zeolite material is in the range of 0.1 wt.% to 15.0 wt.%, more preferably in the range of 0.5 wt.% to 10.0 wt.%, more preferably in the range of 1.5 wt.% to 7.5 wt.%.
[0242] 48. An exhaust gas treatment system according to any one of embodiments 44 to 47, wherein
[0243] In the AMOx coating, the weight ratio of the zeolite material containing one or more of Fe and Cu to the porous oxidic material as defined in Embodiment 42 or 43 is in the range of 0.5:1 to 2:1, preferably in the range of 0.75:1 to 1.5:1, more preferably in the range of 1:1.
[0244] to 1.25:1 range.
[0245] 49. An exhaust gas treatment system according to any one of embodiments 38 to 48, wherein the
[0246] The AMOx coating further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and silica, more preferably silica.
[0247] 50. An exhaust gas treatment system according to embodiment 49, wherein the coating of the third catalyst contains non-zeolitic oxidic material in an amount calculated as oxide in the range of 0.5 wt.% to 18 wt.%, more preferably in the range of 5 wt.% to 16 wt.%, and more preferably in the range of 8 wt.% to 13 wt.%, based on the weight of the AMOx coating of the third catalyst.
[0248] 51. An exhaust gas treatment system according to any one of embodiments 38 to 50, wherein 98 wt % to 100 wt %, preferably 99 wt % to
[0249] 100 wt%, more preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt%
[0250] The present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that the present invention is characterized in that
[0251] 52. An exhaust gas treatment system according to any one of embodiments 38 to 50, wherein the AMOx coating is disposed on the substrate of the third catalyst at more than 98% to 100%, preferably 99% to 100%, and more preferably 99.5% to 100% of the axial length of the substrate, and the SCR coating is disposed on the AMOx coating at more than 98% to 100%, preferably 99% to 100%, and more preferably 99.5% to 100% of the axial length of the substrate.
[0252] 53. An exhaust gas treatment system according to any one of embodiments 1 to 35, wherein the third catalyst includes an inlet zone and an outlet zone, the inlet zone includes the SCR coating, preferably consists of the SCR coating, and the outlet zone includes an ammonia oxidation catalyst coating, preferably consists of an ammonia oxidation catalyst coating.
[0253] 54. An exhaust gas treatment system according to embodiment 53, wherein the inlet zone extends from the inlet end of the substrate toward the outlet end by more than x% of the axial length of the substrate, wherein x is in the range of 20 to 60, preferably in the range of 30 to 55, and more preferably in the range of 45 to 55.
[0254] 55. An exhaust treatment system according to embodiment 54, wherein the outlet zone extends from the outlet end of the substrate toward the inlet end by more than y% of the axial length of the substrate, where y=100-x.
[0255] 56. An exhaust gas treatment system according to any one of embodiments 53 to 55, wherein the SCR coating of the inlet zone comprises, preferably consists of, a zeolite material, preferably having a framework type BEA, comprising iron and non-zeolitic oxide materials, preferably silica and alumina.
[0256] 57. An exhaust gas treatment system according to any one of embodiments 53 to 56, wherein the outlet
[0257] The AMOx coatings in this area include:
[0258] - a first coating comprising a platinum group metal and a zeolite material comprising one or more of Fe and Cu supported on a porous oxidic material;
[0259] - a second coating comprising a zeolitic material containing one or more of Fe and Cu, wherein at most 0.0001 wt. % of the first coating consists of platinum group metals;
[0260] wherein the first coating is disposed on the substrate at a length exceeding the exit zone, and the second coating is disposed on the first coating at a length exceeding the exit zone;
[0261] or wherein the second coating is disposed on the substrate over the length of the exit zone,
[0262] and the first coating is disposed on the second coating with a length exceeding the outlet zone. 58. The exhaust gas treatment system according to embodiment 57, wherein the zeolite material of the second coating of the AMOx coating of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material preferably has a zeolite selected from the group consisting of BEA, MOR, FAU, GME,
[0263] OFF, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably a framework type selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably a framework type selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the AMOx coating of the third catalyst has a framework type BEA.
[0264] 59. An exhaust gas treatment system according to embodiment 58, wherein 95 wt% to 100 wt%, preferably 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt% of the framework structure of the 12-membered ring pore zeolite material contained in the second coating layer of the AMOx coating layer of the third catalyst is composed of Si, Al and O, wherein in the framework structure, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 10:1.
[0265] to 15:1.
[0266] 60. An exhaust gas treatment system according to any one of embodiments 57 to 59, wherein the zeolite material contained in the second coating layer of the AMOx coating layer of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3 based on the total weight of the zeolite material is in the range of 0.1 wt.% to 15.0 wt.%, more preferably in the range of 1.0 wt.% to 10.0 wt.%, more preferably in the range of 3.0 wt.% to 7.5 wt.%.
[0267] 61. An exhaust gas treatment system according to any one of embodiments 57 to 60, wherein at most 0.00001 wt.% of the second coating layer of the AMOx coating of the third catalyst consists of a platinum metal component, wherein preferably 0 wt.% to 0.00001 wt.% of the second coating layer of the AMOx coating of the third catalyst consists of a platinum group metal component.
[0268] 62. The exhaust gas treatment system according to any one of embodiments 57 to 61, wherein the second coating of the AMOx coating of the third catalyst further comprises a non-zeolitic oxidic material, wherein the non-zeolitic oxidic material preferably comprises one or more of zirconium oxide, aluminum oxide, ceria, titanium dioxide, silicon dioxide, and a catalyst comprising Zr, Al, Ce, Ti and
[0269] The mixed oxide of two or more of Si more preferably contains one or more of zirconia, alumina, ceria and silica, more preferably ceria.
[0270] 63. An exhaust gas treatment system according to embodiment 62, wherein the second coating layer of the AMOx coating of the third catalyst contains a non-zeolitic oxidic material in an amount calculated as an oxide in the range of 0.5 wt.% to 12 wt.%, more preferably in the range of 1 wt.% to 10 wt.%, more preferably in the range of 1 wt.% to 6 wt.%, and more preferably in the range of 1 wt.% to 4 wt.%, based on the weight of the second coating layer of the AMOx coating of the third catalyst.
[0271] 64. The exhaust gas treatment system according to any one of embodiments 57 to 63, wherein 98 wt % to 100 wt %, preferably 99 wt %, of the second coating of the AMOx coating of the third catalyst
[0272] % to 100% by weight, more preferably 99.5% to 100% by weight, more preferably 99.9
[0273] % to 100% by weight of a zeolite material comprising one or more of Fe and Cu,
[0274] and preferably consists of a non-zeolitic oxidic material as defined in embodiment 62 or 63.
[0275] 65. The exhaust gas treatment system according to any one of embodiments 57 to 64, wherein the platinum group metal contained in the first coating of the AMOx coating of the third catalyst is Pt, Pd and Rh
[0276] One or more of Pt and Pd, more preferably one or more of Pt.
[0277] 66. The exhaust gas treatment system of embodiment 65, wherein the first coating of the AMOx coating of the third catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 20g / ft 3 In the range of 2g / ft 3 Up to 10g / ft 3 In the range of 3 g / ft 3 Up to 7.5g / ft 3 within the range of platinum group metals.
[0278] 67. An exhaust gas treatment system according to any one of embodiments 57 to 66, wherein the porous oxide material of the first coating layer of the AMOx coating layer of the third catalyst is selected from the group consisting of titanium dioxide, aluminum oxide, ceria, silicon dioxide, zirconium oxide, a mixture of two or more thereof, and a mixed oxide of two or more thereof, preferably selected from the group consisting of titanium dioxide, silicon dioxide and aluminum oxide, more preferably titanium dioxide.
[0279] 68. An exhaust gas treatment system according to any one of embodiments 57 to 67, wherein the first coating layer of the AMOx coating of the third catalyst contains a porous oxidizing material in an amount in the range of 10 wt.% to 80 wt.%, preferably in the range of 30 wt.% to 70 wt.%, and more preferably in the range of 45 wt.% to 55 wt.%, based on the weight of the first coating layer of the AMOx coating of the third catalyst.
[0280] 69. An exhaust gas treatment system according to any one of embodiments 57 to 68, wherein the zeolite material of the first coating layer of the AMOx coating layer of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the second coating layer of the AMOx coating layer of the third catalyst has a framework type BEA.
[0281] 70. An exhaust gas treatment system according to Embodiment 69, wherein 95 wt% to 100 wt%, preferably 98 wt% to 100 wt%, more preferably 99 wt% to 100 wt%, and more preferably 99.5 wt% to 100 wt% of the framework structure of the 12-membered ring pore zeolite material contained in the first coating layer of the AMOx coating of the third catalyst is composed of Si, Al and O, wherein in the framework structure, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 40:1, more preferably in the range of 3:1 to 30:1, more preferably in the range of 4:1 to 20:1, and more preferably in the range of 6:1 to 15:1.
[0282] 71. An exhaust gas treatment system according to any one of embodiments 57 to 70, wherein the zeolite material contained in the first coating layer of the AMOx coating layer of the third catalyst contains iron, wherein the amount of iron contained in the zeolite material calculated as Fe2O3 based on the total weight of the zeolite material is preferably in the range of 1.0 wt.% to 15.0 wt.%, more preferably in the range of 2.0 wt.% to 10.0 wt.%, more preferably in the range of 3.0 wt.% to 7.5 wt.%.
[0283] 72. An exhaust gas treatment system according to any one of embodiments 57 to 71, wherein, in the first coating layer of the AMOx coating layer of the third catalyst, the weight ratio of the zeolite material containing one or more of Fe and Cu to the porous oxide material is in the range of 0.25:1 to 2:1, preferably in the range of 0.5:1 to 1:1.
[0284] 73. An exhaust gas treatment system according to any one of embodiments 57 to 72, wherein the first coating layer of the AMOx coating layer of the third catalyst further comprises a non-zeolitic oxide material, wherein the non-zeolitic oxide material preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si, more preferably comprises one or more of zirconia, alumina, ceria and titania, more preferably silica.
[0285] 74. The exhaust gas treatment system according to embodiment 73, wherein the first coating layer of the AMOx coating of the third catalyst comprises an amount calculated as oxide in the range of 0.5 wt. % to 18 wt. %, more preferably in the range of 5 wt. % to 16 wt. %, more preferably in the range of 8 wt. % to 16 wt. %, based on the weight of the first coating layer of the AMOx coating of the third catalyst.
[0286] 13 wt % of non-zeolitic oxide material.
[0287] 75. An exhaust gas treatment system according to any one of embodiments 57 to 74, wherein 98 wt% to 100 wt%, preferably 99 wt% to 100 wt%, more preferably 99.5 wt% to 100 wt%, and more preferably 99.9 wt% to 100 wt% of the first coating of the AMOx coating of the third catalyst consists of a platinum group metal supported on a porous oxide material, a zeolite material comprising one or more of Fe and Cu, and preferably a non-zeolitic oxide material as defined in embodiment 73 or 74.
[0288] 76. The exhaust treatment system of any one of embodiments 57 to 75, wherein the AMOx coating of the third catalyst consists of a first coating and a second coating.
[0289] 77. The exhaust treatment system according to any one of embodiments 57 to 76, wherein the third catalyst consists of a substrate, an SCR coating and an AMOx coating.
[0290] 78. An exhaust gas treatment system according to any one of embodiments 1 to 37, wherein in addition to the
[0291] In addition to the SCR coating, the third catalyst also includes an oxidation catalyst coating.
[0292] 79. An exhaust gas treatment system according to embodiment 78, wherein the oxidation catalyst coating of the third catalyst comprises a platinum group metal, preferably one or more of Pt, Pd and Rh, more preferably one or more of Pt and Pd, more preferably Pt.
[0293] 80. The exhaust gas treatment system of embodiment 79, wherein the oxidation catalyst coating of the third catalyst comprises a loading of 1 g / ft2 calculated as elemental platinum group metal. 3 Up to 20g / ft 3 In the range of 2g / ft 3 Up to 10g / ft 3 In the range of 3 g / ft 3 Up to 5g / ft 3 within the range of platinum group metals.
[0294] 81. An exhaust gas treatment system according to any one of embodiments 78 to 80, wherein the oxidation catalyst coating of the third catalyst comprises a porous oxidation material, preferably for supporting a platinum group metal as defined in embodiment 79 or 80, more preferably platinum.
[0295] 82. An exhaust gas treatment system according to embodiment 81, wherein the porous oxide material comprises oxygen and one or more of aluminum, titanium, cerium, silicon and zirconium, preferably one or more of aluminum, titanium and silicon, and more preferably aluminum.
[0296] 83. An exhaust gas treatment system according to embodiment 81 or 82, wherein the porous oxide material, preferably a porous oxide material comprising oxygen and aluminum, further comprises a rare earth metal, more preferably one or more of lanthanum, yttrium, cerium, praseodymium, and neodymium, more preferably lanthanum.
[0297] 84. An exhaust gas treatment system according to any one of embodiments 81 to 83, wherein 1 wt% to 6 wt%, preferably 2 wt% to 5 wt%, of the porous material consists of rare earth metals, calculated as oxides.
[0298] 85. A catalyst according to any one of embodiments 81 to 84, wherein 99 wt% to 100 wt%, preferably 99.5 wt% to 100 wt%, more preferably 99.9 wt% to 100 wt% of the porous material consists of oxygen, aluminum and rare earth metals, preferably lanthanum.
[0299] 86. The exhaust gas treatment system according to any one of embodiments 81 to 85, wherein the oxidation catalyst coating of the third catalyst comprises an amount of 0.25 g / in 3 Up to 3g / in 3 In the range of 0.75 g / in 3 Up to 2g / in 3 Porous oxide materials within a range of.
[0300] 87. The exhaust gas treatment system according to any one of embodiments 78 to 86, wherein 98 wt % to 100 wt %, preferably 99 wt %, of the oxidation catalyst coating of the third catalyst
[0301] to 100% by weight, more preferably 99.5% by weight to 100% by weight, more preferably 99.9% by weight
[0302] The present invention is characterized in that the present invention comprises a platinum group metal as defined in Embodiment 79 or 80 and a porous oxide material supporting the platinum group metal as defined in any one of Embodiments 81 to 86.
[0303] 88. An exhaust gas treatment system according to any one of embodiments 78 to 87, wherein the oxidation catalyst coating is disposed on the substrate of the third catalyst at more than 98% to 100%, preferably 99% to 100%, and more preferably 99.5% to 100% of the axial length of the substrate, and the SCR coating is disposed on the oxidation catalyst coating at more than 98% to 100%, preferably 99% to 100%, and more preferably 99.5% to 100% of the axial length of the substrate.
[0304] 89. The exhaust treatment system according to any one of embodiments 78 to 88, wherein the third catalyst consists of a substrate, an SCR coating, and an oxidation catalyst coating.
[0305] 90. An exhaust treatment system according to any one of embodiments 78 to 89, wherein at most 0.01 weight percent, more preferably at most 0.001 weight percent, of the oxidation catalyst coating of the third catalyst is composed of zeolite material, wherein more preferably 0 weight percent to 0.0001 weight percent of the oxidation catalyst coating of the third catalyst is composed of zeolite material.
[0306] 91. A method for simultaneous selective catalytic reduction of NOx, oxidation of hydrocarbons, oxidation of nitrogen monoxide and oxidation of ammonia, the method comprising
[0307] (1) providing an exhaust gas stream from a gasoline engine, the exhaust gas stream comprising one or more of NOx, ammonia, nitrogen monoxide, and hydrocarbons;
[0308] (2) Passing the exhaust gas flow provided in (1) through the exhaust gas system according to any one of Embodiments 1 to 90.
[0309] In the context of the present invention, the term "disposed on a substrate" means that the coating is disposed on the surface of the inner wall of the substrate, wherein the term "surface of the inner wall" is to be understood as the "exposed" or "bare" or "blank" surface of the wall, i.e. the surface of the wall in an untreated state consisting of the material of the wall except for any unavoidable impurities that may contaminate the surface.
[0310] Further, in the context of the present invention, the term "X is one or more of A, B and C", where X is a given feature and each of A, B and C represents a specific implementation of the feature, should be understood to disclose that X is A, or B, or C, or A and B, or A and C, or B and C, or A and B and C. In this regard, it should be noted that a skilled person is able to convert the above abstract terms into specific examples, such as where X is a chemical element and A, B and C are specific elements such as Li, Na and K, or X is a temperature and A, B and C are specific temperatures such as 10°C, 20°C and 30°C. In this regard, it should also be noted that the skilled person is able to expand the above terms to less specific implementations of the features, such as “X is one or more of A and B” discloses that X is A, or B, or A and B, or to more specific implementations of the features, such as “X is one or more of A, B, C, and D” discloses that X is one or more of A, or B, or C, or D, or A and B, or A and C, or A and D, or B and C, or B and D, or C and D, or A and B and C, or A and B and D, or B and C and D.
[0311] Furthermore, in the context of the present invention, the term "consisting of" with respect to the weight % of one or more components indicates the amount of the weight % of the component based on 100 weight % of the entity in question. For example, the phrase "wherein 0 weight % to 0.001 weight % of the second coating layer consists of platinum" indicates that out of 100 weight % of the components constituting the coating layer, 0 weight % to 0.001 weight % is platinum.
[0312] Furthermore, in the context of the present invention, the term "closely coupled" catalyst is used herein to define a catalyst that is the first catalyst to receive the exhaust gas stream exhausted from the engine.
[0313] The present invention is further illustrated by the following examples. Example
[0314] Analysis-Measurement
[0315] 1.1 Determination of BET specific surface area of alumina
[0316] The BET specific surface area of aluminum oxide is determined in accordance with DIN 66131 or DIN-ISO 9277 using liquid nitrogen.
[0317] 1.2 Determination of volume-based particle size distribution Dv90
[0318] The particle size distribution was determined by static light scattering using a Sympatec HELOS / BR-OM & QUIXEL wet dispersion apparatus equipped with a laser (HeNe) diffraction sensor with a 31 channel multi-element detection range comprising 5 modules covering 0.1 micron to 875 micron.
[0319] Reference Example 1 Three-Way Conversion (TWC) Catalyst
[0320] The aqueous mixture of palladium salt precursor and rhodium salt precursor was impregnated on high porosity alumina and ceria-zirconia. The obtained mixture of Pd / Rh on alumina (100% high porosity alumina) and ceria-zirconia (solid content: 60 wt % to 75 wt %) was calcined at 400° C. to 600° C. for 2 to 4 hours.
[0321] The mixture is prepared by mixing water, n-octanol and a barium oxide precursor and zirconium oxide. The amount of the barium oxide precursor is calculated so that the final loading of BaO in the catalyst after calcination is 1% to 10% by weight based on the weight of the coating, and the amount of the zirconium oxide precursor is calculated so that the loading of ZrO2 from the source in the catalyst after calcination is 1% to 5% by weight based on the weight of the coating. The obtained calcined Pd / Rh on alumina and / or ceria-zirconia is added to the mixture comprising n-octanol to obtain a slurry. The slurry solid content is adjusted to 30% to 50% by weight to enhance pH and viscosity measurements and wet grinding. After grinding, the pH of the slurry is adjusted to a pH of 3 to 5 by adding nitric acid. The particle size distribution (Dv90) of the slurry after grinding is 10 microns to 20 microns.
[0322] The obtained slurry was placed on the entire length of an uncoated ceramic honeycomb flow-through substrate (diameter: 4.66 inches x length: 2.5 inches, cylindrical substrate with 750 / (2.54) cm2). 2The coating was prepared by coating with a thickness of 0.0635 mm (2.5 mils) above 100 mm, dried at 120°C to 180°C and further calcined at 400°C to 600°C in air. The final coating contained high porosity alumina, ceria-zirconia, Pd, Rh, zirconium oxide and barium oxide. The coating loading was 1.5 g / in 3 Up to 4g / in 3 .
[0323] Reference Example 2 Four-Way Conversion (FWC) Catalyst
[0324] The aqueous mixture of palladium salt precursor and rhodium salt precursor is impregnated on high porosity alumina and ceria-zirconia. The obtained mixture of Pd / Rh on alumina and ceria-zirconia (solid content: 50 wt % to 80 wt %) is calcined at 400° C. to 600° C. for 2 to 4 hours.
[0325] The mixture is prepared by mixing water, n-octanol and a barium oxide precursor and zirconium oxide. The amount of the barium oxide precursor is calculated so that the final loading of BaO in the catalyst after calcination is 1% to 5% by weight based on the weight of the coating, and the amount of the zirconium oxide precursor is calculated so that the loading of ZrO2 from the source in the catalyst after calcination is 1% to 5% by weight based on the weight of the coating. The obtained calcined Pd / Rh on alumina and / or ceria-zirconia is added to the mixture comprising n-octanol to obtain a slurry. The slurry solid content is adjusted to 30% to 50% by weight to enhance pH and viscosity measurements and wet grinding. After grinding, the pH of the slurry is adjusted to a pH of 3 to 5 by adding nitric acid. The particle size distribution (Dv90) of the slurry after grinding is 7 microns to 18 microns.
[0326] The obtained slurry was placed on the entire length of an uncoated ceramic honeycomb wall flow substrate (diameter: 4.66 inches x length: 4.26 inches, a cylindrical substrate with 300 / (2.54) 2 The coating was prepared by calcining the quartz crystals at 120°C to 180°C and further calcining at 400°C to 600°C in air. The final coating contained high porosity alumina, ceria-zirconia, Pd, Rh, zirconium oxide, and barium oxide. The coating loading was 1 g / in 3 Up to 3g / in 3 .
[0327] Comparative Example 1: Exhaust gas treatment system not according to the present invention
[0328] The exhaust gas treatment system of Comparative Example 1 includes the catalyst (TWC catalyst) of Reference Example 1 as Catalyst 1, the catalyst (FWC catalyst) of Reference Example 2 as Catalyst 2, and the catalyst (TWC catalyst) of Reference Example 1 as Catalyst 3, wherein Catalyst 1 is located upstream of Catalyst 2 and Catalyst 2 is located upstream of Catalyst 3. There is no catalyst between Catalyst 1 and Catalyst 2 and between Catalyst 2 and Catalyst 3, and Catalyst 1 is a tightly coupled catalyst. The system is Figure 1 Shown in.
[0329] Reference Example 3 Ammonia Oxidation (AMOx) Catalyst
[0330] Base coating with PGM :
[0331] The aqueous mixture of the Pt precursor is impregnated on a high surface area and porous oxidic support such as alumina, titania, ceria-zirconia or a mixture of these in an aqueous medium. The solid content of the obtained mixture is 50% to 70%. The slurry is wet milled such as to obtain a Dv90 of 10 microns to 25 microns. Further, separately, appropriate amounts of Fe-BEA (Fe content, calculated as Fe2O3: 1.5 wt% to 7.5 wt% based on the weight of the zeolite, and a molar ratio of silica to alumina of 6-15:1) and silica (8 wt% to 13 wt% based on the weight of the PGM-containing coating, calculated as SiO2) are mixed in distilled water to obtain a mixture with a solid content of 30% to 50%. The BEA-containing mixture and the Pt-containing mixture are mixed and wet milled such as to obtain a particle size distribution Dv90 of 2 microns to 15 microns. The obtained slurry was then placed over the entire length of an uncoated ceramic honeycomb flow-through substrate (diameter: 5.66 inches x length: 3 inches, cylindrical substrate with 400 / (2.54) 2 The PGM coating was prepared by drying at 120°C to 180°C and calcining at 400°C to 600°C in air. The PGM coating loading was 1 g / in 3 Up to 3g / in 3 .
[0332] PGM-free top coating :
[0333] A mixture of ceria precursor (1 to 4 wt. %, calculated as CeO2, based on the weight of the PGM-free coating) and distilled water is prepared and Fe-BEA zeolite (Fe content, calculated as Fe2O3: 1.5 to 7.5 wt. % based on the weight of the zeolite, silica to alumina molar ratio of 6-15:1) is added to the mixture under constant mixing. The solid content of the obtained slurry is 20 to 40%. The slurry is dispersed and mixed such as to obtain a Dv90 of 2 to 12 microns. The obtained slurry is then placed over the entire length of the substrate coated with the PGM-containing bottom coating, dried at 120 to 180°C and calcined in air at 400 to 600°C. The loading of the PGM-free coating is 1 g / in 3 Up to 3g / in 3 .
[0334] Reference Example 4 Selective Catalytic Reduction (SCR) / AMOx Catalyst
[0335] SCR coating :
[0336] A mixture of distilled water and Fe-BEA zeolite (Fe content, calculated as Fe2O3: 1.5 wt% to 7.5 wt% based on the weight of the zeolite, a molar ratio of silica to alumina of 6-15:1) is prepared, to which silica and alumina powders are added as small amounts of additives. The amount of additives is calculated so that the amount of silica + alumina in the SCR coating is 1 wt% to 5 wt% calculated as oxides (SiO2, Al2O3) based on the weight of the SCR coating. The solid content of the obtained mixture is 30% to 50%. The slurry is wet ground such as to obtain a Dv90 of 3 to 18 microns.
[0337] The obtained slurry was placed on the entire length of an uncoated ceramic honeycomb flow-through substrate (diameter: 5.66 inches×length: 3 inches, cylindrical substrate with 400 / (2.54) cm2) from the inlet end of the substrate toward the outlet end of the substrate. 2 The SCR coating comprises Fe-BEA zeolite, alumina and silica. The loading of the SCR coating is 2 g / in 3 Up to 4g / in 3 .
[0338] AMOx coating :
[0339] PGM-containing bottom coating: prepared as in Reference Example 3
[0340] PGM-free top coating: prepared as in Reference Example 3
[0341] The obtained slurry for the PGM bottom coating was placed over 50% of the entire length of the ceramic honeycomb flow-through substrate coated with the SCR coating from the outlet end of the substrate toward the inlet end of the substrate, and the obtained slurry for the PGM-free top coating was placed over 50% of the entire length of the ceramic honeycomb flow-through substrate coated on top of the PGM bottom coating. The loading amount of the AMOx coating was 2.5 g / in 3 Up to 4g / in 3 .
[0342] Reference Example 5 Selective Catalytic Reduction (SCR) Catalyst
[0343] A mixture of distilled water and Fe-BEA zeolite (Fe content, calculated as Fe2O3: 1.5 wt% to 7.5 wt% based on the weight of the zeolite) is prepared, to which a zirconium oxide precursor is added as an additive. The amount of the zirconium oxide precursor is calculated so that the amount of zirconium oxide in the catalyst is 1 wt% to 5 wt% based on the weight of the coating. The solid content of the obtained mixture is 30% to 45%. The slurry is ground such as to obtain a Dv90 of 3 to 12 microns.
[0344] The obtained slurry was placed on the entire length of an uncoated ceramic honeycomb flow-through substrate (diameter: 4.66 inches x length: 3 inches, cylindrical substrate with 400 / (2.54) 2 The SCR coating comprises Fe-BEA zeolite and zirconium oxide. The loading of the SCR coating is 2 g / in 3 Up to 4g / in 3 .
[0345] Reference Example 6 Ammonia Oxidation (AMOx) Catalyst
[0346] Base coating with PGM :
[0347] The aqueous mixture of the Pt precursor is impregnated on a high surface area and porous oxidic support such as alumina, preferably La-doped alumina (4 wt. % La calculated as La2O3 based on the weight of the support) in an aqueous medium. The solid content of the obtained mixture is 50% to 70%. The slurry is wet milled such as to obtain a Dv90 of 2 to 25 microns. The obtained slurry is then placed on the entire length of an uncoated ceramic honeycomb flow-through substrate (diameter: 5.66 inches x length: 3 inches, a cylindrical substrate with 400 / (2.54) per square centimeter. 2The PGM coating was prepared by drying at 120°C to 180°C and calcining at 400°C to 600°C in air. The PGM coating loading was 1 g / in 3 Up to 2g / in 3 .
[0348] PGM-free top coating :
[0349] A mixture of zirconium oxide precursor (2 to 5 wt. %, calculated as ZrO2, based on the weight of the PGM-free coating) and distilled water is prepared and Fe-BEA zeolite (Fe content, calculated as Fe2O3: 1.5 to 7.5 wt. %, based on the weight of the zeolite, and a silica to alumina molar ratio of 6-15:1) is added to the mixture under constant mixing. The solid content of the obtained slurry is 20 to 40%. The slurry is dispersed and mixed such as to obtain a Dv90 of 2 to 12 microns. The obtained slurry is then placed over the entire length of the substrate coated with the PGM-containing bottom coating, dried at 120 to 180°C and calcined in air at 400 to 600°C. The loading of the PGM-free coating is 1.5 g / in 3 Up to 3g / in 3 .
[0350] Reference Example 7 Selective Catalytic Reduction (SCR) Catalyst
[0351] A mixture of distilled water and Cu-CHA zeolite (Cu content, calculated as CuO: 3.4 wt% based on the weight of the zeolite) was prepared, to which a zirconium oxide precursor was added as an additive. The amount of the zirconium oxide precursor was calculated so that the amount of zirconium oxide in the catalyst was 1 wt% to 5 wt% based on the weight of the coating. The solid content of the obtained mixture was 42%. The slurry was ground such as to obtain a Dv90 of 3 to 12 microns.
[0352] The obtained slurry was placed on the entire length of an uncoated ceramic honeycomb flow-through substrate (diameter: 4.66 inches x length: 3 inches, cylindrical substrate with 400 / (2.54) 2 The SCR coating comprises Cu-CHA zeolite and zirconium oxide. The loading of the SCR coating is 2 g / in 3 .
[0353] Comparative Example 2 Exhaust gas treatment system not according to the present invention
[0354] The exhaust gas treatment system of Comparative Example 2 includes the catalyst of Reference Example 1 (TWC catalyst) as Catalyst 1, the catalyst of Reference Example 2 (FWC catalyst) as Catalyst 2, and the catalyst of Reference Example 7 (SCR catalyst) as Catalyst 3, wherein Catalyst 1 is located upstream of Catalyst 2 and Catalyst 2 is located upstream of Catalyst 3. There is no catalyst between Catalyst 1 and Catalyst 2 and between Catalyst 2 and Catalyst 3, and Catalyst 1 is a tightly coupled catalyst.
[0355] Example 1 Exhaust gas treatment system according to the present invention
[0356] The exhaust gas treatment system of Example 1 includes the catalyst of Reference Example 1 (TWC catalyst) as Catalyst 1, the catalyst of Reference Example 2 (FWC catalyst) as Catalyst 2, and the catalyst of Reference Example 3 (AMOx catalyst) as Catalyst 3, wherein Catalyst 1 is located upstream of Catalyst 2 and Catalyst 2 is located upstream of Catalyst 3. There is no catalyst between Catalyst 1 and Catalyst 2 and between Catalyst 2 and Catalyst 3. Catalyst 1 is a tightly coupled catalyst. The system is Figure 1 Shown in.
[0357] Example 2 Exhaust gas treatment system according to the present invention
[0358] The exhaust gas treatment system of Example 2 includes the catalyst of Reference Example 1 (TWC catalyst) as Catalyst 1, the catalyst of Reference Example 2 (FWC catalyst) as Catalyst 2, and the catalyst of Reference Example 3 (SCR / AMOx catalyst) as Catalyst 4, wherein Catalyst 1 is located upstream of Catalyst 2, and Catalyst 2 is located upstream of Catalyst 3. There is no catalyst between Catalyst 1 and Catalyst 2 and between Catalyst 2 and Catalyst 3. Catalyst 1 is a tightly coupled catalyst. The system is Figure 1 Shown in.
[0359] Example 3 Exhaust gas treatment system according to the present invention
[0360] The exhaust gas treatment system of Example 3 includes the catalyst of Reference Example 1 (TWC catalyst) as Catalyst 1, the catalyst of Reference Example 2 (FWC catalyst) as Catalyst 2, and the catalyst of Reference Example 3 (SCR catalyst) as Catalyst 5, wherein Catalyst 1 is located upstream of Catalyst 2 and Catalyst 2 is located upstream of Catalyst 3. There is no catalyst between Catalyst 1 and Catalyst 2 and between Catalyst 2 and Catalyst 3. Catalyst 1 is a tightly coupled catalyst. The system is Figure 1 Shown in.
[0361] Example 4 HC and NH3 Tailpipe Emissions at WLTC—Systems According to Examples 1 to 3 and Comparative Example 1 Test
[0362] In different systems, Catalyst 1 (TWC) and Catalyst 2 (FWC) are located in the same tank with different combinations of downstream components in Comparative Example 1 and Examples 1 to 3. The comparative system containing TWC and FWC and downstream of TWC represents a standard Euro 6 configuration, while the inventive system consisting of AMOx, SCR or a combination of both in an underfloor position downstream of TWC+FWC represents a Euro 7 gasoline application.
[0363] The systems evaluated were aged on an engine bench using a 2L Euro 6 engine, such that the tank containing TWC+FWC was placed in the CC position, while the components under evaluation (TWC, AMOx, SCR+AMOx or SCR) were placed downstream in separate tanks. For all systems studied, the same CC unit was used upstream. Aging was of lambda 1 type with periodic fuel cuts or lean / rich perturbations, with a downstream catalyst inlet temperature of 830°C. Aging duration was 20h. Thermocouples placed at different locations along the exhaust line recorded the engine outlet, catalyst inlet and bed temperatures.
[0364] The system and therefore component evaluation (WLTC) was performed on a Euro 6GTDI vehicle using a chassis dyno test cell. The latter was equipped with thermoelectric elements and FT-IR units at the engine outlet / catalyst inlet, catalyst bed and outlet positions, allowing accurate recording of temperatures and gas emissions along the exhaust line.
[0365] The data presented includes each system using the WLTC cycle collected on the above vehicles ( Figure 1 ) of accumulated HC and NH3( Figures 2 to 3 )emission.
[0366] As from Figure 2 It can be seen that the cumulative HC emissions obtained with the comparative system are significantly higher than those of the inventive system, especially at low speeds and temperatures up to 200 seconds in the WLTC cycle. The best results were obtained with the SCR downstream only configuration containing the highest Fe-BEA loading, indicating that the excellent low temperature HC tailpipe reduction is directly related to the zeolite loading. Thus, using the system according to the invention, the total HC emissions are greatly reduced under the evaluated conditions in the WLTC cycle. Finally, as can be seen from Figure 3 It can be seen that the cumulative NH3 multi-emissions are significantly higher for the comparative system compared to the new inventive system according to the present invention. The best results were obtained with the AMOx downstream system, while the highest emissions were created on the SCR only underfloor system.
[0367] Thus, it has been demonstrated that the system according to the invention comprising an AMOx catalyst, or an SCR catalyst, or both, downstream of a TWC+FWC CC1 configuration allows for improved HC and NOx conversions. Without wishing to be bound by any theory, it is believed that the PGM-free zeolite coating in the downstream position plays a key role in this process.
[0368] Example 5 Exhaust gas treatment system according to the present invention
[0369] The exhaust gas treatment system of Example 1 includes the catalyst of Reference Example 1 (TWC catalyst) as Catalyst 1, the catalyst of Reference Example 2 (FWC catalyst) as Catalyst 2, and the catalyst of Reference Example 3 (AMOx catalyst) as Catalyst 6, wherein Catalyst 1 is located upstream of Catalyst 2 and Catalyst 2 is located upstream of Catalyst 3. There is no catalyst between Catalyst 1 and Catalyst 2 and between Catalyst 2 and Catalyst 3. Catalyst 1 is a tightly coupled catalyst.
[0370] Example 6 HC and NH3 Tailpipe Emissions at WLTC—Testing of Systems According to Example 3 and Comparative Example 2
[0371] In different systems, Catalyst 1 (TWC) and Catalyst 2 (FWC) were located in the same tank with different downstream component combinations in Comparative Example 2 and Example 3. The Comparative system contained a Cu-CHA SCR catalyst and Inventive Example 3 contained a Fe-BEA SCR catalyst.
[0372] The systems evaluated were aged on an engine bench using a 2L Euro 6 engine, so that the tank containing the TWC+FWC was placed in the CC position, while the SCR component under evaluation was placed downstream in a separate tank. For all systems studied, the same CC unit was used upstream. The aging was of the lambda 1 type with periodic fuel cuts or lean / rich perturbations, with a downstream catalyst inlet temperature of 820°C. The aging duration was 80h. Thermocouples placed at different locations along the exhaust line recorded the engine outlet, catalyst inlet and bed temperatures.
[0373] The system and therefore component evaluation (WLTC) was performed on a Euro 6GTDI vehicle using a chassis dyno test cell. The latter was equipped with thermoelectric elements and FT-IR units at the engine outlet / catalyst inlet, catalyst bed and outlet positions, allowing accurate recording of temperatures and gas emissions along the exhaust line.
[0374] The data presented includes each system using the WLTC cycle collected on the above vehicles ( Figure 1 ) of accumulated NH3, CO and N2O ( Figures 4 to 6 ) emissions. Figures 4 to 6It can be seen that compared with Example 3 of the present invention, the cumulative NH3, CO and N2O emissions of Comparative Example 2 are significantly higher.
[0375] It has thus been demonstrated that the system according to the invention comprising a Fe-BEA SCR catalyst downstream of a TWC+FWC CC1 configuration allows improving the NH 3 , CO and N 2 O conversions. BRIEF DESCRIPTION OF THE DRAWINGS
[0376] Figure 1 Schematic diagrams of exhaust gas treatment systems according to Comparative Example 1 and Examples 1 to 3 are shown.
[0377] Figure 2 The accumulated HC obtained with the systems of Examples 1 to 3 and Comparative Example 1 after aging is shown.
[0378] Figure 3 The accumulated NH3 obtained after aging using the systems of Examples 1 to 3 and Comparative Example 1 is shown.
[0379] Figure 4 The accumulated NH3 obtained after aging using the systems of Example 3 and Comparative Example 2 are shown.
[0380] Figure 5 The accumulated CO obtained with the systems of Example 3 and Comparative Example 2 after aging is shown.
[0381] Figure 6 The accumulated N2O obtained after aging using the systems of Example 3 and Comparative Example 2 is shown.
Claims
1. An exhaust gas treatment system for treating an exhaust gas flow leaving a gasoline engine, the exhaust gas treatment system having an upstream end for introducing the exhaust gas flow into the exhaust gas treatment system, wherein the exhaust gas treatment system comprises (i) a first catalyst, the first catalyst being a three-way conversion catalyst having an inlet end and an outlet end and comprising a coating disposed on a substrate, wherein the coating comprises a platinum group metal component supported on a porous oxidic material; (ii) a second catalyst, which is a four-way conversion catalyst having an inlet end and an outlet end and comprising a washcoat disposed on a wall flow filter substrate, wherein the washcoat comprises a platinum group metal component supported on a porous oxidic material; (iii) a third catalyst having an inlet end and an outlet end, wherein the third catalyst comprises a substrate and a washcoat for selective catalytic reduction of NOx, wherein the SCR washcoat comprises a zeolite material comprising one or more of Fe and Cu, wherein at most 0.0001 wt. % of the SCR washcoat consists of a platinum group metal; wherein the first catalyst according to (i) is the first catalyst of the exhaust treatment system downstream of the upstream end of the exhaust treatment system, and wherein the inlet end of the first catalyst is arranged upstream of the outlet end of the first catalyst; wherein in the exhaust gas treatment system, the second catalyst according to (ii) is located downstream of the first catalyst according to (i), and wherein the inlet end of the second catalyst is arranged upstream of the outlet end of the second catalyst; wherein in the exhaust gas treatment system, the third catalyst according to (iii) is located downstream of the second catalyst according to (ii), and wherein the inlet end of the third catalyst is arranged upstream of the outlet end of the third catalyst.
2. The exhaust gas treatment system according to claim 1, wherein the porous oxide material of the platinum group metal component of the coating layer supporting the first catalyst is selected from the group consisting of aluminum oxide, ceria, silica, zirconium oxide, titanium oxide, a mixture of two or more thereof, and a mixed oxide of two or more thereof, preferably selected from the group consisting of aluminum oxide, titanium oxide, zirconium oxide, a mixture of two or more thereof, and a mixed oxide of two or more thereof, more preferably selected from the group consisting of aluminum oxide, zirconium oxide, a mixture of two of them, and a mixed oxide of two of them, more preferably aluminum oxide.
3. An exhaust gas treatment system according to claim 1 or 2, wherein the coating of the first catalyst further comprises an oxygen storage component, the oxygen storage component preferably comprises cerium, more preferably comprises one or more of cerium oxide, a mixture of oxides including cerium oxide, and a mixed oxide comprising cerium, wherein the mixed oxide comprising cerium more preferably further comprises one or more of zirconium, yttrium, neodymium, lanthanum, hafnium, samarium and praseodymium, more preferably one or more of zirconium, yttrium, neodymium, lanthanum and praseodymium, more preferably zirconium.
4. The exhaust gas treatment system according to claim 3, wherein in the coating of the first catalyst, the weight ratio of the porous oxidizing material as defined in claim 3 to the oxygen storage component is in the range of 1:1 to 10:1, preferably in the range of 1:1 to 5:
1.
5. The exhaust gas treatment system according to any one of claims 1 to 4, wherein the coating of the first catalyst further comprises an oxide of an alkaline earth metal, the alkaline earth metal is preferably selected from the group consisting of barium, strontium and magnesium, more preferably selected from the group consisting of barium and strontium, more preferably barium.
6. An exhaust gas treatment system according to any one of claims 1 to 5, wherein the coating of the second catalyst further comprises an oxygen storage component (OSC), the oxygen storage component preferably comprising cerium, more preferably comprising one or more of cerium oxide, a mixture of oxides including cerium oxide, and a mixed oxide comprising cerium, wherein the mixed oxide comprising cerium more preferably further comprises one or more of zirconium, yttrium, neodymium, lanthanum, hafnium, samarium and praseodymium, more preferably one or more of zirconium, yttrium, neodymium, lanthanum and praseodymium, more preferably zirconium.
7. The exhaust gas treatment system according to any one of claims 1 to 6, wherein the zeolite material contained in the SCR coating of the third catalyst is a 12-membered ring pore zeolite material, wherein the 12-membered ring pore zeolite material preferably has a framework type selected from the group consisting of BEA, MOR, FAU, GME, OFF, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA, MOR, FAU, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of BEA and FAU, wherein more preferably the 12-membered ring pore zeolite material contained in the SCR coating of the third catalyst has a framework type BEA. 8 . The exhaust gas treatment system according to claim 7 , wherein the zeolite material contained in the SCR coating of the third catalyst is a 12-membered ring pore zeolite material, and the zeolite material contains Fe.
9. The exhaust gas treatment system according to any one of claims 1 to 8, wherein the third catalyst consists of the substrate and the SCR coating.
10. The exhaust gas treatment system according to any one of claims 1 to 8, wherein the third catalyst comprises an ammonia oxidation catalyst (AMOx) coating in addition to the SCR coating.
11. The exhaust gas treatment system according to claim 10, wherein the SCR coating of the third catalyst comprises, preferably consists of, a zeolitic material, preferably of framework type BEA, containing iron and a non-zeolitic oxide material, preferably ceria.
12. The exhaust gas treatment system according to claim 10 or 11, wherein the AMOx coating of the third catalyst comprises a platinum group metal, preferably one or more of Pt, Pd and Rh, more preferably one or more of Pt and Pd, more preferably Pt, and further comprises a zeolite material containing one or more of Fe and Cu, preferably a zeolite material containing Fe.
13. The exhaust gas treatment system according to any one of claims 10 to 12, wherein the AMOx coating of the third catalyst comprises a porous oxidic material, preferably for supporting the platinum group metal as defined in claim 11, wherein the porous oxidic material is selected from the group consisting of titanium dioxide, aluminum oxide, ceria, silicon dioxide, zirconium oxide, a mixture of two or more thereof, and a mixed oxide of two or more thereof, preferably selected from the group consisting of titanium dioxide, aluminum oxide and silicon dioxide, more preferably titanium dioxide.
14. An exhaust gas treatment system according to claim 13, insofar as it is dependent on claim 11, wherein: In the AMOx coating, a weight ratio of the zeolite material comprising one or more of Fe and Cu to the porous oxidic material is in the range of 0.5:1 to 2:1, preferably in the range of 0.75:1 to 1.5:1, and more preferably in the range of 1:1 to 1.25:
1.
15. The exhaust gas treatment system according to any one of claims 10 to 14, wherein the AMOx coating is disposed on the substrate of the third catalyst at more than 98% to 100%, preferably 99% to 100%, and more preferably 99.5% to 100% of the axial length of the substrate, and the SCR coating is disposed on the AMOx coating at more than 98% to 100%, preferably 99% to 100%, and more preferably 99.5% to 100% of the axial length of the substrate.
16. The exhaust gas treatment system according to any one of claims 1 to 8, wherein the third catalyst comprises an inlet zone and an outlet zone, the inlet zone comprising the SCR coating, preferably consisting of the SCR coating, and the outlet zone comprising an ammonia oxidation catalyst coating, preferably consisting of an ammonia oxidation catalyst coating; wherein the AMOx coating of the outlet zone comprises: - a first coating comprising a platinum group metal and a zeolitic material comprising one or more of Fe and Cu supported on a porous oxidic material, preferably titania, the first coating preferably further comprising a non-zeolitic oxidic material, wherein the non-zeolitic oxidic material more preferably comprises one or more of zirconia, alumina, ceria, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ce, Ti and Si; - a second coating comprising a zeolitic material containing one or more of Fe and Cu, wherein at most 0.0001 wt. % of the first coating consists of platinum group metals; wherein the first coating is disposed on the substrate with a length exceeding the outlet zone, and the second coating is disposed on the first coating with a length exceeding the outlet zone; or wherein the second coating is disposed on the substrate with a length exceeding the outlet zone, and the first coating is disposed on the second coating with a length exceeding the outlet zone.
17. An exhaust gas treatment system according to any one of claims 1 to 8, wherein in addition to the SCR coating, the third catalyst further comprises an oxidation catalyst coating; wherein the oxidation catalyst coating of the third catalyst comprises a platinum group metal, and wherein at most 0.01 weight % of the oxidation catalyst coating of the third catalyst consists of a zeolite material.
18. A method for the simultaneous selective catalytic reduction of NOx, oxidation of hydrocarbons, oxidation of nitrogen monoxide and oxidation of ammonia, the method comprising (1) providing an exhaust gas stream from a gasoline engine, the exhaust gas stream comprising one or more of NOx, ammonia, nitrogen monoxide, and hydrocarbons; (2) The exhaust gas flow provided in (1) is passed through the exhaust gas system according to any one of claims 1 to 17.